Ink composition, production method thereof, and composite and electronic device prepared therefrom
By using combined nanoparticles containing silver, germanium, selenium and sulfur, and siliconizing reaction with organic ligands containing aromatic groups and fluorine, the problem of insufficient optical performance and stability of nanoparticles in the prior art is solved, and the development of high-efficiency fluorescent nanoparticles is achieved, and it is suitable for the manufacturing of a variety of electronic devices.
Patent Information
- Application Number
- JP2024159140
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-09-15
- Filing Date
- 2024-09-13
- Publication Date
- 2025-03-28
AI Technical Summary
It is difficult to develop efficient fluorescent nanoparticles that do not contain harmful heavy metals such as bismuth, and the optical properties and stability of these nanoparticles are insufficient.
Combined nanoparticles containing silver, germanium, selenium and sulfur are used, and stable nanoparticles are formed by siliconization reaction with organic ligands containing aromatic groups and fluorine.
It has achieved improved optical performance and stability of high-efficiency fluorescent nanoparticles, avoided the use of harmful heavy metals, and is suitable for the manufacturing of a variety of electronic devices.
Smart Images

Figure 2025043332000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to an ink composition, a method for producing the same, and a composite and an electronic device produced therefrom. [Background technology]
[0002] Semiconductor nanoparticles can exhibit physical properties (e.g., energy band gap, melting point) that are known as intrinsic properties of a material, that differ from bulk materials. For example, semiconductor nanoparticles can be configured to emit light upon energy excitation (e.g., irradiation with light or application of voltage). Such nanoparticles can find potential applications in a variety of devices (e.g., electronic devices). It is desirable to develop luminescent nanoparticles that can achieve improved luminescent properties from an environmental perspective and that do not contain hazardous heavy metals such as cadmium. Summary of the Invention [Problem to be solved by the invention]
[0003] One embodiment provides an ink composition containing semiconductor nanoparticles that can exhibit improved physical properties (optical properties such as absorptivity or stability). One embodiment provides a method for making the ink composition. One embodiment provides a composite made from the ink composition. One embodiment provides an electronic device (eg, a display device) comprising the composite. [Means for solving the problem]
[0004] According to an embodiment, the ink composition includes semiconductor nanoparticles, a first organic ligand, and a polymerizable monomer, the semiconductor nanoparticles include (a 11-13-16 group compound including) silver, indium, gallium, and sulfur, and the first organic ligand includes an aromatic group and fluorine. In the ink composition, the content of the semiconductor nanoparticles may be 2% by weight or more and 70% by weight or less based on the total weight of the ink composition.
[0005] The first organic ligand can further include a functional group configured to bind or coordinate to a surface of the semiconductor nanoparticle. The first organic ligand is capable of binding or coordinating to a surface of the semiconductor nanoparticle.
[0006] The semiconductor nanoparticles may further include zinc. The semiconductor nanoparticles may have a charge balance value (total cations / total anions) of 0.8 or more and 1.8 or less, or 1.5 or less, as represented by the formula: charge balance value={[Ag]+3x([In]+[Ga]))+2[Zn]} / (2x[S]) where [Ag], [In], [Ga], [Zn], and [S] are the molar contents of silver, indium, gallium, zinc, and chalcogen elements, respectively, in the semiconductor nanoparticles.
[0007] The charge balance value can be 0.9 or more, 1 or more, 1.1 or more, or 1.3 or more. The charge balance value can be 1.7 or less, 1.6 or less, 1.55 or less, 1.3 or less, 1.2 or less, or 1.1 or less.
[0008] In the semiconductor nanoparticles, the molar ratio of zinc to the sum of zinc, indium, gallium, and silver (Zn / (In+Ga+Ag+Zn), hereinafter referred to as relative zinc molar ratio) may be 0.25 or more, 0.3 or more, or 0.4 or more and 0.9 or less, or 0.65 or less. The molar ratio of zinc to sulfur (Zn / S) in the semiconductor nanoparticles may be 0.9 or less, 0.8 or less, 0.3 or less, or 0.25 or less.The molar ratio of zinc to sulfur in the semiconductor nanoparticles may be 0.01 or more, 0.05 or more, 0.1 or more, 0.3 or more, or 0.4 or more.
[0009] The semiconductor nanoparticles may have a molar ratio of zinc to indium (Zn / In) of 0.1 or more, 1 or more, 2.5 or more, 3.5 or more, or 3.9 or more. The semiconductor nanoparticles may have a molar ratio of zinc to indium of 20 or less, 10 or less, 8 or less, 7.5 or less, or 5.7 or less.
[0010] In the semiconductor nanoparticles, a molar ratio of zinc (Zn) to silver (Ag) (Zn / Ag) can be 0.3 or more, 0.5 or more, and 5 or less, 3.5 or less, or 2 or less. In the semiconductor nanoparticles, a molar ratio of sulfur to the sum of silver, indium, and gallium (S / (Ag+In+Ga)) may be 1.3 or more, or 1.35 or more and 2.5 or less, 2.4 or less, or 2 or less.
[0011] In the semiconductor nanoparticles, the combined molar ratio of indium and gallium to silver ((In+Ga) / Ag) may be 1.5 or more, 1.8 or more, and 7.0 or less, 3.5 or less, 2 or less. The semiconductor nanoparticles may have a molar ratio of silver to indium (Ag / In) of 0.01 or more, 0.03 or more, 0.1 or more, and 0.5 or less, or 0.3 or less. The semiconductor nanoparticles may have a molar ratio of gallium to indium (Ga / In) of 2 or more, 2.5 or more, or 3 or more and 10 or less, 5 or less, or 4 or less.
[0012] In the semiconductor nanoparticles, the molar ratio of gallium to the sum of indium and gallium (Ga / (In+Ga)) may be 0.95 or less, 0.8 or less, and the molar ratio of gallium to the sum of indium and gallium may be 0.5 or more, 0.65 or more, or 0.7 or more.
[0013] The semiconductor nanoparticles may have a molar ratio of sulfur to indium (S / In) of 3 or more, 5 or more, 7 or more, and 25 or less, 20 or less, or 15 or less. The semiconductor nanoparticles may have a molar ratio of gallium to sulfur (Ga / S) of 1 or less, 0.8 or less, 0.5 or less, 0.45 or less, or 0.41 or less. The molar ratio of gallium to sulfur (Ga / S) may be 0.1 or more, 0.3 or more, or 0.35 or more.
[0014] The semiconductor nanoparticles may be free of lithium. The semiconductor nanoparticles may be free of sodium. The semiconductor nanoparticles may be free of alkali metals. The semiconductor nanoparticles may be free of copper, or may further include copper.
[0015] The semiconductor nanoparticles are configured to emit a first light (eg, green light or red light). The semiconductor nanoparticles or the first light may have a peak emission wavelength in the range of 500 nm or more and 650 nm or less. The peak emission wavelength of the first light (or the green light) may be in the range of 505 nm or more and 580 nm or less. The peak emission wavelength of the first light (or the red light) may be in the range of 600 nm or more and 650 nm or less.
[0016] The semiconductor nanoparticles or the first light may have a half-width of 5 nm or more and 70 nm or less. The semiconductor nanoparticles are configured to exhibit a quantum yield of 50% or more. The semiconductor nanoparticles may exhibit an (absolute) quantum yield of 60% or more. The quantum yield may be 62% or more, 65% or more, 70% or more, 80% or more, or 85% or more. The quantum yield may be 100% or less, or 99% or less.
[0017] The half width may be 45 nm or less, 40 nm or less, 35 nm or less, 33 nm or less, or 31 nm or less. The half width may be 5 nm or more, 10 nm or more, 15 nm or more, or 25 nm or more.
[0018] The first organic ligand can include a compound represented by Formula 1: [Chemical formula 1] AL-Ar In the above formula, A is a functional group configured to interact with (e.g., bind to) the surface of the semiconductor nanoparticle; L includes a single bond, a substituted or unsubstituted aliphatic hydrocarbon group having 1 to 40 (or 2 to 20) carbon atoms (e.g., an alkylene group, an alkenylene group, or an alkynylene group), a substituted or unsubstituted aromatic hydrocarbon group having 6 to 40 (6 to 20) carbon atoms, a substituted or unsubstituted alicyclic hydrocarbon group having 3 to 40 (3 to 20) carbon atoms, -CO-, -O-, -COO-, -S-, -SO-, -NHCO-, -NH-, or a combination thereof; Ar is a fluorine-containing aromatic group having 6 to 40 (6 to 20) carbon atoms.
[0019] In the above formula, A is a carboxyl group (-COOH), an amine group (-NRH), a thiol group (-SH), a hydroxyl group (-OH), -P(O)(OR). 2 , -PR 2 , -P(O)R 2 or a residue derived therefrom (e.g., -COO - , -NR - , -S - , -O - , -P(O)(OR)O - etc.) (wherein R can include hydrogen or an aliphatic hydrocarbon group having 1 to 30 carbon atoms, such as an alkyl group, an alkenyl group, or an alkynyl group, an aromatic hydrocarbon group having 6 to 30 carbon atoms, such as an aryl group, or a combination thereof) or a combination thereof.
[0020] The first organic ligand can include a compound represented by formula 2-1: [ka]
[0021] In the above formula, A is a functional group configured to interact with (e.g., bind to) the surface of the semiconductor nanoparticle; L includes a single bond, a substituted or unsubstituted aliphatic hydrocarbon group having 1 to 40 (or 2 to 20) carbon atoms (e.g., an alkylene group, an alkenylene group, or an alkynylene group), a substituted or unsubstituted aromatic hydrocarbon group having 6 to 40 (6 to 20) carbon atoms, a substituted or unsubstituted alicyclic hydrocarbon group having 3 to 40 (3 to 20) carbon atoms, -CO-, -O-, -COO-, -S-, -SO-, -NHCO-, -NH-, or a combination thereof; Flu can include a fluoro group (-F), a fluorine-substituted hydrocarbon group having 1 to 20 carbon atoms (e.g., a fluorine-substituted aliphatic hydrocarbon group having 1 to 20 carbon atoms or a fluorine-substituted aromatic hydrocarbon group having 6 to 20 carbon atoms), or a combination thereof. The fluorine-substituted hydrocarbon group having 1 to 20 carbon atoms can include one or more fluorine substituents bonded to the hydrocarbon group having 1 to 20 carbon atoms. In formula 2-1, n can be 1, 2, 3, 4, or 5. In the chemical formula 1 or the chemical formula 2-1, the substituted or unsubstituted aliphatic hydrocarbon group having 1 to 20 carbon atoms contains one or more methylene (-CH 2 -) may be replaced with -CO-, -O-, -COO-, -S-, -SO-, -NHCO-, -NH-, or combinations thereof.
[0022] The first organic ligand may or may not include an acrylate residue. The first organic ligand may further include a carboxy group or a residue derived therefrom (eg, a carboxylate group) (hereinafter abbreviated as a carboxy group). The first organic ligand may be attached to a surface of the semiconductor nanoparticle.
[0023] The first organic ligand may include fluorobenzoic acid, a fluorophenyl carboxylic acid compound, a phenyl carboxylic acid compound substituted with a fluoroalkyl group, a phenyl carboxylic acid compound substituted with a fluoroalkenyl group, a phenyl carboxylic acid compound substituted with a fluoroalkynyl group, a mercaptofluorobenzene, a fluorophenyl thiol compound, a phenyl thiol compound substituted with a fluoroalkyl group, a phenyl thiol compound substituted with a fluoroalkenyl group, a phenyl thiol compound substituted with a fluoroalkynyl group, or a combination thereof;
[0024] The first organic ligand may not include an amine group. The first organic ligand can be a compound having a carbon number of 100 or less, 50 or less, 30 or less, or 20 or less. The first organic ligand can have a molecular weight of 50 g / mol or more and 300 g / mol or less.
[0025] In the ink composition, the content of the semiconductor nanoparticles may be 3 wt % or more, 5 wt % or more, 10 wt % or more, 14 wt % or more, 15 wt % or more, or 20 wt % or more based on the total weight of the composition. In the ink composition, the content of the semiconductor nanoparticles may be 65 wt % or less or 50 wt % or less based on the total weight of the composition.
[0026] In the ink composition, the content of the first organic ligand may be 5 wt % or more, 10 wt % or more, 15 wt % or more, or 20 wt % or more and 50 wt % or less, 30 wt % or less, or 25 wt % or less, based on the total weight of the semiconductor nanoparticles.
[0027] In the ink composition, the monomer has the formula: [ka]
[0028] In the above Chemical Formula 3, X is an organic group having 2 to 30 carbon atoms and a carbon-carbon double bond, L 2 is a single bond, a carbon atom, a substituted or unsubstituted alkylene group having 1 to 50 carbon atoms, a substituted or unsubstituted alkenylene group having 1 to 50 carbon atoms, a substituted or unsubstituted cycloalkylene group having 3 to 50 carbon atoms (e.g., 6 to 30 carbon atoms), a substituted or unsubstituted cycloalkenylene group having 3 to 50 carbon atoms (e.g., 6 to 30 carbon atoms), a substituted or unsubstituted arylene group having 6 to 50 carbon atoms, a substituted or unsubstituted heteroarylene group having 3 to 30 carbon atoms, a group having one or more oxyalkylene units [(RO)n, where R is a substituted or unsubstituted alkylene group having 1 to 10 carbon atoms such as methylene, ethylene, isopropylene, butylene, etc., and n is 1 or more, 3 or more, 5 or more, 10 or more, and 500 or less, 300 or less, 100 or less, 50 or less, or 15 or less], sulfonyl (-S(=O) 2 -), carbonyl (-C(=O)-), ether (-O-), sulfide (-S-), sulfoxide (-S(=O)-), ester (-C(=O)O-), amide (-C(=O)NR-) (wherein R is hydrogen or a straight or branched chain alkyl group having 1 to 10 carbon atoms), imine (-NR-) (wherein R is hydrogen or a straight or branched chain alkyl group having 1 to 10 carbon atoms), or a combination thereof; Y is a single bond, a substituted or unsubstituted alkylene group having 1 to 30 carbon atoms, a substituted or unsubstituted alkenylene group having 2 to 30 carbon atoms, or a sulfonyl (-S(=O) 2 -), carbonyl (-C(=O)-), ether (-O-), sulfide (-S-), sulfoxide (-S(=O)-), ester (-C(=O)O-), amide (-C(=O)NR-) (wherein R is hydrogen or a straight or branched chain alkyl group having 1 to 10 carbon atoms), imine (-NR-) (wherein R is hydrogen or a straight or branched chain alkyl group having 1 to 10 carbon atoms), or a combination thereof; n is an integer equal to or greater than 1 (e.g., 1, 2, or 3); k is an integer equal to or greater than 1 (e.g., 1, 2, or 3); The sum of n and k is an integer of 2 or greater (eg, 3 or greater, or 4 or greater and 10 or less, or 5 or less). n is determined by the valence of Y. k is determined by the valence of L. X can include a vinyl group, a (meth)acrylate group, or a combination thereof.
[0029] The monomers include polyethylene glycol methacrylate, polypropylene glycol methacrylate, polyethylene glycol dimethacrylate, polypropylene glycol dimethacrylate, substituted or unsubstituted alkyl (meth)acrylate, ethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, 1,4-butanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, neopentyl glycol di(meth)acrylate, pentaerythritol di(meth)acrylate, pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, and the like. The acrylate or acrylate combination may include glyceryl ether, glyceryl ether, acrylate, dipentaerythritol di(meth)acrylate, dipentaerythritol tri(meth)acrylate, dipentaerythritol penta(meth)acrylate, dipentaerythritol hexa(meth)acrylate, bisphenol A epoxy acrylate, bisphenol A di(meth)acrylate, trimethylolpropane tri(meth)acrylate, novolac epoxy (meth)acrylate, ethyl glycol monomethyl ether (meth)acrylate, tris(meth)acryloyloxyethyl phosphate, propylene glycol di(meth)acrylate, diacryloyloxyalkane, or combinations thereof.
[0030] In one embodiment, the monomer may be a photopolymerizable monomer, and may include a substituted or unsubstituted di(meth)acrylate compound, a substituted or unsubstituted tri(meth)acrylate compound, a substituted or unsubstituted tetra(meth)acrylate compound, a substituted or unsubstituted penta(meth)acrylate compound, a substituted or unsubstituted hexa(meth)acrylate compound, or a combination thereof.
[0031] In the ink composition, the content of the monomer may be 1 wt % or more and 99 wt % or less, for example, 3 wt % or more or 70 wt % or less, based on the total weight of the composition. The ink composition can further include an initiator, metal oxide particles, or a combination thereof.
[0032] The ink composition may or may not include an organic solvent, e.g., a volatile organic solvent. In one embodiment, the total solids content of the ink composition may be 50% or more, 75% or more, 80% or more, 95% or more, 99% or more, or 100% based on the total weight of the composition. The total solids content is the amount (e.g., by weight) of non-volatile materials (i.e., components excluding organic solvents, e.g., monomers, polymeric materials, nanoparticles, or other additives (if present)) included in a given composition. The content of the initiator may be 0.5% by weight or more and 10% by weight or less, based on the total weight of the composition. The content of the metal oxide particles may be 0.5% by weight or more and 30% by weight or less, based on the total weight of the composition.
[0033] The ink composition can provide a semiconductor nanoparticle-polymer composite or a pattern thereof, which includes a matrix containing a polymerization product of the monomer and semiconductor nanoparticles arranged or dispersed in the matrix. The semiconductor nanoparticle-polymer composite can be heat-treated at 180° C. for 30 minutes, and the retention rate obtained by the following formula can be 95% or more, or 100% or more: Retention rate (%)=[EQE2 / EQE1]×100 In the above formula, EQE1 is the external quantum efficiency of the semiconductor nanoparticle-polymer composite before heat treatment after polymerization, and EQE2 is the external quantum efficiency of the semiconductor nanoparticle-polymer composite after heat treatment.
[0034] In one embodiment, the semiconductor nanoparticle-polymer composite comprises a matrix, semiconductor nanoparticles disposed (e.g., dispersed) within the matrix, and fluorine, the semiconductor nanoparticles comprising a Group 11-13-16 compound including silver, indium, gallium, and sulfur. The content of the semiconductor nanoparticles in the composite can be 1 wt % or more, or 5 wt % or more and 70 wt % or less, or 50 wt % or less, based on the total weight of the composite.
[0035] The semiconductor nanoparticle-polymer composite or the semiconductor nanoparticle may further include a first organic ligand. The semiconductor nanoparticle may further include fluorine. Details regarding the semiconductor nanoparticles are as described herein. Details regarding the first organic ligand are as described herein. The semiconductor nanoparticle-polymer composite or the ink composition can have a molar ratio of fluorine to indium (F / In) greater than 0, greater than 0.2, 0.21 or greater, 0.25 or greater, 0.3 or greater, 0.5 or greater, 1 or greater, 1.5 or greater, 2 or greater, 2.5 or greater, or 3 or greater. The semiconductor nanoparticle-polymer composite or the ink composition can have a molar ratio of fluorine to indium (F / In) of 10 or less, 5 or less, 4 or less, 2.6 or less, 2 or less, 1.5 or less, 1 or less, or 0.8 or less.
[0036] The semiconductor nanoparticle-polymer composite or the ink composition can have a molar ratio of fluorine to silver (F / Ag) greater than 0, greater than or equal to 0.3, greater than or equal to 0.35, greater than or equal to 0.4, greater than or equal to 0.9, greater than or equal to 0.95, greater than or equal to 1, or greater than or equal to 1.2. The semiconductor nanoparticle-polymer composite or the ink composition can have a molar ratio of fluorine to silver (F / Ag) of 5 or less, 3 or less, 2 or less, 1.5 or less, 1 or less, or 0.8 or less.
[0037] The semiconductor nanoparticle-polymer composite or the ink composition can have a molar ratio of fluorine to sulfur (F / S) greater than 0, greater than or equal to 0.09, greater than or equal to 0.12, greater than or equal to 0.35, greater than or equal to 0.45, or greater than or equal to 0.55. The semiconductor nanoparticle-polymer composite or the ink composition may have a molar ratio of fluorine to sulfur (F / S) of 5 or less, 2 or less, 1.5 or less, 1 or less, 0.65 or less, 0.57 or less, 0.49 or less, 0.42 or less, or 0.3 or less.
[0038] The semiconductor nanoparticle-polymer composite may have an external quantum efficiency (EQE) of 27% or more, or 30% or more (e.g., when the composite is placed in an integrating hemisphere and irradiated with incident light of a given wavelength (e.g., 450 nm)) as given by the following formula: External quantum efficiency (%) = [A / B] x 100 A: The amount of the first light emitted from the complex B: Amount of incident light The semiconductor nanoparticle-polymer composite may have an internal quantum efficiency (IEQ) of 29% or more, or 35% or more (e.g., when the composite is placed in an integrating hemisphere and irradiated with incident light of a given wavelength (e.g., 450 nm)) as given by the following formula: Internal quantum efficiency (%) = [A / (B-B')] x 100 A: The amount of the first light emitted from the complex B: Amount of incident light B': Amount of incident light that passed through the complex The semiconductor nanoparticle-polymer composite or the ink composition may have an incident light absorptance of 70% or more, 80% or more, 85% or more, or 90% or more, or 91% or more, given by the following formula: Incident light absorption rate (%) = [(B-B') / B] x 100 B: Amount of incident light B': Amount of incident light that passed through the complex The composite may have an incident light absorptance of 70%-100%, 80%-98%, 95%-99%, 96%-98%, or a combination thereof. The composite may have an incident light absorptance of 85% or greater.
[0039] The semiconductor nanoparticles may have an (average) particle size of 1 nm or more and 10 nm or less. The semiconductor nanoparticles may have a half-width of 40 nm or less, 35 nm or less, or 31 nm or less (e.g., 15 nm to 33 nm or 20 nm to 32 nm) when confirmed by, for example, their emission spectrum. The semiconductor nanoparticles may have a quantum yield of more than 85%. The semiconductor nanoparticles may have a quantum yield of 87% or more and 98% or less.
[0040] One embodiment provides a color conversion layer (e.g., color conversion structure) including a color conversion region including the semiconductor nanoparticles or a composite including the same as described above. In one embodiment, a color conversion panel includes a color conversion layer (e.g., color conversion structure) including a color conversion region and optionally a partition defining each region of the color conversion layer. The color conversion region includes a first region corresponding to a first pixel, the first region including a first composite configured to emit a first light, and the first composite includes the semiconductor nanoparticle-polymer composite described above.
[0041] Another embodiment provides a display device including a light source and the composite. In one embodiment, the display panel includes a light emitting panel (or light source), the color conversion panel, and optionally a light-transmitting layer located between the light emitting panel and the color conversion panel. The light emitting panel (or light source) is configured to provide excitation light (or incident light) to the color conversion panel. The excitation light (or incident light) may include blue light and optionally green light. The blue light may have a peak wavelength in the range of 440 nm to 460 nm or 450 nm to 455 nm. The light source may include organic light emitting diodes, micro LEDs, mini LEDs, LEDs including nanorods, or combinations thereof.
[0042] In one embodiment, an electronic device (or display device) includes the color conversion panel or the display panel. In one embodiment, the display device may include a VR device, an AR device, a mobile terminal device, a monitor, a notebook computer, a television, an electronic display, a camera, or an electrical component for a vehicle. Effect of the Invention
[0043] The ink composition according to an embodiment may provide a semiconductor nanoparticle-polymer composite or a pattern thereof that exhibits improved physical properties in an inkjet system. The ink composition according to an embodiment may exhibit improved processability (e.g., process retention rate). The semiconductor nanoparticle-polymer composite according to an embodiment may exhibit improved optical properties as well as thermal stability. [Brief description of the drawings]
[0044] [Figure 1a] FIG. 2 is a schematic cross-sectional view of a color conversion panel according to a non-limiting embodiment. [Figure 1b] 1 is a cross-sectional view of an electronic device (display device) according to a non-limiting embodiment. [Diagram 2] FIG. 1 is a diagram illustrating a pattern formation process (by inkjet printing) using an ink composition according to one embodiment. [Figure 3a] 1 is a perspective view illustrating an example of a display panel including a color conversion panel according to an embodiment. [Figure 3b] FIG. 13 is an exploded view of a display element according to another embodiment. [Figure 4a] FIG. 3b is a cross-sectional view of the display panel of FIG. 3a. [Figure 4b] FIG. 2 is an exploded view of a display element (including mini LEDs) according to one embodiment. [Figure 5a] FIG. 3b is a plan view showing an example of a pixel arrangement of the display panel of FIG. 3a. [Figure 5b] FIG. 2 is a cross-sectional view showing an example of a light-emitting element. [Figure 5c] FIG. 2 is a cross-sectional view showing an example of a light-emitting element. [Figure 5d] FIG. 2 is a cross-sectional view showing an example of a light-emitting element. [Figure 5e] FIG. 2 is a cross-sectional view showing an example of a light-emitting element. [Figure 6] 5b is a cross-sectional view of the display panel of FIG. 5a taken along line IV-IV. [Figure 7] 1 is a schematic cross-sectional view of a display element (for example, a liquid crystal display element) according to an embodiment. [Figure 8] FIG. 2 shows XPS results for the semiconductor nanoparticle-polymer composites produced in the examples and comparative examples. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0045] The advantages and features of the technology described below, and the methods of achieving them, may become clear by referring to the embodiments described in detail below with the accompanying drawings. However, it can be said that the realized form is not limited to the embodiments disclosed below. Unless otherwise defined, all terms (including technical and scientific terms) used in this specification can be used as a meaning commonly understood by those having ordinary knowledge in the relevant technical field. In addition, terms defined in commonly used dictionaries are not interpreted ideally or excessively unless clearly defined otherwise. Throughout the specification, when a part "includes" a certain component, this means that it can further include other components, not excluding other components, unless otherwise specified to the contrary.
[0046] In the drawings, the thickness of layers and regions are exaggerated for clarity, and the same reference numbers are used throughout the specification to refer to similar parts. When a part such as a layer, film, region, or plate is said to be "on" another part, this includes not only when it is "directly on" the other part, but also when there are other parts in between. Conversely, when a part is said to be "directly on" another part, it means that there are no other parts in between. Additionally, the singular includes the plural unless the phrase specifically dictates otherwise. Thus, a reference to a "semiconductor nanoparticle" can refer to one semiconductor nanoparticle or a plurality of semiconductor nanoparticles, and a reference to a "metal oxide particle" can refer to one metal oxide particle or a plurality of metal oxide particles.
[0047] Here, the statement "free of cadmium (or other toxic heavy metals)" can refer to a concentration of cadmium (or the heavy metal) of 100 ppm (by weight) or less, 50 ppm or less, 10 ppm or less, 1 ppm or less, 0.1 ppm or less, 0.01 ppm or less, or approximately 0. In one embodiment, there is substantially no cadmium (or the heavy metal), or if present, it is present in an amount or impurity level below the detection limit of a given detection means.
[0048] Unless otherwise defined below, "substituted" means that a hydrogen atom in a compound is replaced by an alkyl group having 1 to 30 carbon atoms, an alkenyl group having 2 to 30 carbon atoms, an alkynyl group having 2 to 30 carbon atoms, an aryl group having 6 to 30 carbon atoms, an alkylaryl group having 7 to 30 carbon atoms, an alkoxy group having 1 to 30 carbon atoms, a heteroalkyl group having 1 to 30 carbon atoms, a heteroalkylaryl group having 3 to 30 carbon atoms, a cycloalkyl group having 3 to 30 carbon atoms, a cycloalkenyl group having 3 to 15 carbon atoms, a cycloalkynyl group having 6 to 30 carbon atoms, a heterocycloalkyl group having 2 to 30 carbon atoms, a halogen (-F, -Cl, -Br, or -I), a hydroxy group (-OH), a nitro group (-NO 2 ), cyano group (-CN), amino group (-NRR', where R and R' are each independently hydrogen or an alkyl group having 1 to 6 carbon atoms), azide group (-N 3 ), amidino group (-C(=NH)NH 2 ), hydrazino group (-NHNH 2 ), hydrazono group (=N(NH 2 ), aldehyde group (-C(=O)H), carbamoyl group (-C(O)NH 2), thiol group (-SH), ester group (-C(=O)OR, where R is an alkyl group having 1 to 6 carbon atoms or an aryl group having 6 to 12 carbon atoms), carboxyl group (-COOH) or a salt thereof (-C(=O)OM, where M is an organic or inorganic cation), sulfonic acid group (-SO 3 H) or its salt (-SO 3 M, where M is an organic or inorganic cation), a phosphate group (-PO 3 H 2 ) or its salt (-PO 3 MH or -PO 3 M 2 wherein M is an organic or inorganic cation), and combinations thereof.
[0049] Also, unless otherwise defined below, "hetero" means containing 1 to 3 heteroatoms selected from N, O, S, Si, and P.
[0050] Here, the "aliphatic hydrocarbon group" can include a monovalent or polyvalent (e.g., divalent) group (e.g., an alkyl group or an alkylene group) derived from an alkane (e.g., linear or branched chain) (e.g., having 1 to 50 carbon atoms, 2 to 40 carbon atoms, or 3 to 30 carbon atoms), a monovalent or polyvalent (e.g., divalent) group (e.g., an alkenyl group or an alkenylene group) derived from an alkene (e.g., linear or branched chain) (e.g., having 1 to 50 carbon atoms, 2 to 40 carbon atoms, or 3 to 30 carbon atoms), or a monovalent or polyvalent (e.g., divalent) group (e.g., an alkynyl group or an alkynylene group) derived from an alkyne (e.g., linear or branched chain) (e.g., having 1 to 50 carbon atoms, 2 to 40 carbon atoms, or 3 to 30 carbon atoms). Here, the term "aromatic hydrocarbon group" or "aromatic group" can include a monovalent or polyvalent (e.g., divalent) group derived from an allene having 6 to 30 carbon atoms (e.g., an aryl group, an arylene group, etc.) or a monovalent or polyvalent (e.g., divalent) group derived from a heteroallene having 2 to 30 carbon atoms (e.g., a heteroaryl group, a heteroarylene group, etc.). Examples of "aromatic hydrocarbon groups" or "aromatic groups" include phenyl, phenylene, naphthyl, anthracenyl, phenanthrenyl, pyrenyl, chrysenyl, pyridinyl, pyridinylene, pyrimidinyl, pyrazinyl, pyrazinylene, pyridazinyl, triazinyl, quinolinyl, quinolinylene, isoquinolinyl, isoquinolinylene, etc. Heteroarenes can be cyclic aromatic systems having 1 to 30 carbon atoms and containing one or more heteroatoms selected from N, O, P, and S as ring-forming atoms. As used herein, "alicyclic hydrocarbon group" refers to a monovalent or polyvalent (e.g., divalent) group derived from a carbocyclic ring system (or a heterocarbon ring system) having 3 to 40 or 3 to 20 carbon atoms and, optionally, a heteroatom selected from among N, O, P, and S.Examples of alicyclic hydrocarbon groups include a cyclopentyl group, a cyclopentylene group, a cyclohexyl group, a cyclohexylene group, a cycloheptyl group, a cycloheptylene group, a cyclooctyl group, a cyclooctylene group, a bicycloundecanyl group, a bicylcoundecanylene group, a cyclopropenyl group, a cyclopropenylene group, a cyclobutenyl group, a cyclobutenylene group, a cyclopentenyl group, a cyclopentenylene group, a cyclohexenyl group, a cyclohexenylene group, a cycloheptenyl group, a cycloheptenylene group, a cyclooctenyl group, a cyclooctenylene group, a tricylcodecanyl group, and a tricyclodecanylene group.
[0051] Here, the term "(meth)acrylate" refers to both acrylate and / or methacrylate. As used herein, "Group" refers to a Group of the Periodic Table of the Elements.
[0052] Here, a nanoparticle or nanostructure refers to a structure having at least one region or characteristic dimension with a nanoscale dimension. In one embodiment, the dimension of the nanostructure may be less than about 500 nm, less than about 300 nm, less than about 250 nm, less than about 150 nm, less than about 100 nm, less than about 50 nm, or less than about 30 nm. Such structures may have any shape. The nanoparticle or nanostructure may have any shape, including, but not limited to, nanowires, nanorods, nanotubes, multipod-type shapes having two or more pods, nanodots, and the like. The nanoparticle or nanostructure may be, for example, substantially crystalline, substantially monocrystalline, polycrystalline, amorphous, or a combination thereof.
[0053] Here, quantum dots refer to nanocrystalline particles (e.g., semiconductor-based) that exhibit quantum confinement or exciton confinement, and are a type of luminescent (e.g., capable of emitting light upon energy excitation) nanoparticles. Here, quantum dots or semiconductor nanoparticles are not limited in shape unless otherwise specified.
[0054] Here, the term "dispersion" refers to a dispersion in which the dispersed phase is a solid and the continuous medium is a liquid or a solid different from the dispersed phase. Here, the term "dispersion" can be a colloidal dispersion in which the dispersed phase has dimensions of 1 nm or more, for example, 2 nm or more, 3 nm or more, or 4 nm or more, and a few micrometers (um) or less (for example, 2 um or less, or 1 um or less, 900 nm or less, 800 nm or less, 700 nm or less, 600 nm or less, or 500 nm or less).
[0055] Here, the dimensions (size, thickness, etc.) may be values for a single entity or may be averages for multiple particles, where average may be median or mean. In one embodiment, average may be mean.
[0056] Here, the peak emission wavelength refers to the wavelength at which the light emission spectrum reaches its maximum value.
[0057] Here, quantum efficiency is easily and reproducibly determined using commercially available equipment (e.g., from Hitachi or Hamamatsu, etc.) and, for example, by referring to the manual provided by each equipment manufacturer. Quantum efficiency (or quantum yield) is measured in solution or solid state (in a complex). In one embodiment, quantum efficiency (or quantum yield) is the ratio of photons emitted to photons absorbed by a semiconductor nanoparticle or a group of them. In one embodiment, quantum efficiency can be measured by any method. For example, there can be two types of methods for fluorescence quantum yield or efficiency: absolute method and relative method. In this specification, quantum efficiency measured by absolute method is called absolute quantum efficiency.
[0058] In the absolute method, the fluorescence of all samples is detected through an integrating sphere to obtain the quantum efficiency. In the relative method, the fluorescence intensity of a standard dye (standard specimen) is compared with the fluorescence intensity of an unknown sample to calculate the quantum efficiency of the unknown sample. Coumarin 153, Coumarin 545, Rhodamine 101 inner salt, Anthracene and Rhodamine 6G are some of the standard dyes used due to their PL wavelengths, but are not limited to these.
[0059] The half-width and emission peak wavelength (eg, PL or EL wavelength) can be measured by an emission (eg, light emission) spectrum obtained by a spectrophotometer, such as, for example, a fluorescence spectrophotometer. Here, the "first absorption peak wavelength" refers to the wavelength of the first main peak that appears in the lowest energy region of the UV-Vis absorption spectrum.
[0060] Nanoparticles are included in a variety of electronic devices. The electrical and / or optical properties of nanoparticles can vary depending on their physical properties (e.g., composition, size, and / or shape). In one embodiment, the semiconductor nanoparticles can be semiconductor nanocrystal particles. Semiconductor nanoparticles, such as quantum dots, have a large surface area per unit volume and can exhibit quantum confinement effects, which can result in physical properties that differ from bulk materials of the same composition. For example, nanoparticles, such as quantum dots, can absorb energy (e.g., light) from an excitation source, enter an energy excited state, and emit energy corresponding to their band gap energy.
[0061] The semiconductor nanoparticles can also be used in various electronic devices, such as color conversion panels (e.g., light-emitting color filters). For example, in a display device including a quantum dot-based color conversion panel or emissive color filter, instead of a white light-emitting backlight unit of a liquid crystal display device, a quantum dot layer, which is a light-emitting material, is disposed in front of the device, and blue light (excitation light) provided from a light source is converted into green light or red light by the quantum dot layer. In such a color conversion panel, the color conversion of the excitation light is performed in a relatively forward part of the device, so that the viewing angle problem of the liquid crystal display can be solved by forward scattering of light, and the light loss problem of an absorptive color filter can also be solved. In this specification, a color conversion panel can mean an electronic device including a color conversion layer. Here, the color conversion layer also includes a structure including a color conversion region (e.g., a color conversion structure).
[0062] In a display device including such a color conversion panel, the physical properties (e.g., optical properties and stability, etc.) of the luminescent material can directly affect the display quality of the device. For example, the luminescent material included in the color conversion panel disposed relatively forward of the device may be required to have an improved level of absorptivity for excitation light as well as luminous efficiency. When applied to a patterned single film such as a color filter, a decrease in the absorptivity of the excitation light directly causes blue leakage in the display device and negatively affects the color reproduction rate (e.g., DCI matching rate), and the use of an absorptive color filter to prevent blue leakage may result in an additional decrease in luminescent efficiency. The decreased absorptivity of nanoparticles may lead to decreased brightness in devices including them.
[0063] Many of the semiconductor nanoparticles that can exhibit properties (optical properties and / or stability) that can be applied to devices contain cadmium-based compounds (e.g., cadmium chalcogenides). Cadmium poses serious environmental / health problems and is one of the regulated elements. Therefore, in-depth research has been conducted on nanocrystals based on III-V compounds for cadmium-free environmentally friendly nanoparticles. However, there is a technical need for the development of environmentally friendly nanoparticles that can exhibit increased absorptance, achieve narrower half-widths, and exhibit high levels of luminescence efficiency compared to non-cadmium semiconductor nanoparticles based on III-V compounds (e.g., indium phosphide).
[0064] A color conversion panel (e.g., a self-luminous color filter) can be manufactured by a photolithography method or an inkjet printing method using a composition including quantum dots. The photolithography method can provide a precise color filter with reproducibility. The photolithography method requires coating, exposure, development, and curing for each (sub)pixel, which can affect manufacturing time and cost. The inkjet printing method can produce nanoparticle-composites in a desired pattern by depositing liquid ink discharged through an inkjet head at a predetermined position. The inkjet printing method is advantageous in terms of manufacturing process, time, and cost because it can simultaneously provide pixels that show different colors such as red, green, and blue. Therefore, it is desirable to develop an ink composition that can produce a composite that has enhanced process stability and can show improved luminescence properties for the nanoparticles of the novel composition.
[0065] An ink composition according to an embodiment can provide semiconductor nanoparticle-polymer composites or patterns thereof that can exhibit improved optical properties (e.g., external quantum efficiency and internal quantum efficiency) in a simpler manner with increased process stability.
[0066] In one embodiment, the ink composition comprises semiconductor nanoparticles, a first organic ligand, and a polymerizable monomer, the semiconductor nanoparticles comprise silver, indium, gallium, and sulfur (including 11-13-16 group compounds), the first organic ligand comprises an aromatic group and fluorine, and the content of the semiconductor nanoparticles in the ink composition is 1 wt % or more, 1.5 wt % or more, or 2 wt % or more and 70 wt % or less based on the total weight of the ink composition. The first organic ligand is coordinated to or bonded to the surface of the semiconductor nanoparticles. The first organic ligand may include a functional group configured to bond to the surface of the semiconductor nanoparticles. Thus, one embodiment relates to semiconductor nanoparticles comprising the first organic ligand on a surface thereof.
[0067] In one embodiment, the semiconductor nanoparticle-polymer composite can include a matrix and semiconductor nanoparticles disposed (e.g., dispersed) within the matrix. The semiconductor nanoparticles can include 11-13-16 group compounds including silver, indium, gallium, and sulfur. The semiconductor nanoparticle-polymer composite or the semiconductor nanoparticles can further include fluorine or a fluorine-containing organic ligand. The semiconductor nanoparticles in the composite can have a content of 1 wt % or more, 1.5 wt % or more, or 2 wt % or more and 70 wt % or less, or 50 wt % or less, based on the total weight of the composite. In one embodiment, the semiconductor nanoparticle-polymer composite can be prepared by polymerizing the ink composition.
[0068] In some embodiments, the semiconductor nanoparticles may be free of cadmium. In some embodiments, the semiconductor nanoparticles may be free of mercury, lead, or a combination thereof. In some embodiments, the semiconductor nanoparticles may further include zinc. In some embodiments, the semiconductor nanoparticles may or may not include lithium. The semiconductor nanoparticles may or may not include an alkali metal, such as sodium, potassium, etc. The semiconductor nanoparticles may or may not include copper.
[0069] The semiconductor nanoparticles of an embodiment are configured to emit a first light. The first light may be green light. The first light may be red light. The semiconductor nanoparticles of an embodiment may achieve improved optical properties (e.g., narrow half-width, increased quantum yield, and blue light absorptivity) while emitting light of a desired wavelength range. The semiconductor nanoparticles of an embodiment may be utilized as various color conversion (or wavelength downward conversion) materials, such as color conversion panels or color conversion sheets, and may exhibit increased absorptivity per light-emitting particle weight, so that devices such as panels or sheets including the same may be manufactured at reduced cost and provide improved photoconversion.
[0070] The semiconductor nanoparticles may have a concentration gradient in which the indium content varies (e.g., decreases) in the radial direction (e.g., from the center to the periphery). In one embodiment, the indium content in the portion adjacent to the surface (e.g., the shell layer or the outermost layer) may be less than the indium content in the inner portion of the particle. In one embodiment, the portion adjacent to the surface (e.g., the shell layer or the outermost layer) may be free of indium. The semiconductor nanoparticles may further include zinc. The zinc content in the portion adjacent to the surface of the semiconductor nanoparticles may be greater than the zinc content in the inner portion of the particle. In one embodiment, the inner portion or core of the particle may be free of zinc.
[0071] In one embodiment, the semiconductor nanoparticles may have a core-shell structure, and may include a first semiconductor nanocrystal (or a core comprising the first semiconductor nanocrystal) and a shell comprising (e.g., disposed on or surrounding the first semiconductor nanocrystal) a second semiconductor nanocrystal.
[0072] The first semiconductor nanocrystals may include silver, a Group 13 metal (e.g., indium, gallium, or a combination thereof), and a chalcogen element (e.g., sulfur, optionally selenium). The first semiconductor nanocrystals may include a four-member alloy semiconductor material based on a Group 11-13-16 compound including silver (Ag), indium, gallium, and sulfur. The molar ratio between each component in the first semiconductor nanocrystals may be adjusted so that the final nanoparticles exhibit the desired composition and optical properties.
[0073] The size (e.g., size or average size) of the first semiconductor nanocrystals or cores can be 0.5 nm or more, 1 nm or more, 1.5 nm or more, 1.7 nm or more, 1.9 nm or more, 2 nm or more, 2.1 nm or more, 2.3 nm or more, 2.5 nm or more, 2.7 nm or more, 2.9 nm or more, 3 nm or more, 3.1 nm or more, 3.3 nm or more, 3.5 nm or more, 3.7 nm or more, or 3.9 nm or more. The size of the first semiconductor nanocrystals can be 5 nm or less, 4.5 nm or less, 4 nm or less, 3.5 nm or less, 3 nm or less, 2.5 nm or less, 2 nm or less, or 1.5 nm or less.
[0074] The shell may include a second semiconductor nanocrystal including a Group 13 metal (indium, gallium, or a combination thereof) and a chalcogen element (sulfur, optionally selenium). The second semiconductor nanocrystal may further include silver (Ag). The second semiconductor nanocrystal may include silver, gallium, and sulfur. The second semiconductor nanocrystal may include a ternary alloy semiconductor material including silver, gallium, and sulfur. The second semiconductor nanocrystal may include a Group 13-16 compound, a Group 11-13-16 compound, or a combination thereof. The Group 13-16 compound may include gallium sulfide, gallium selenide, indium sulfide, indium selenide, indium gallium sulfide, indium gallium selenide, indium gallium selenide sulfide, or a combination thereof. The shell may further include a third semiconductor nanocrystal including zinc, gallium, and sulfur. The second semiconductor nanocrystal and the third semiconductor nanocrystal may have a different composition than the first semiconductor nanocrystal. The second semiconductor nanocrystal can have a different composition than the third semiconductor nanocrystal. The shell (e.g., the second semiconductor nanocrystal, the third semiconductor nanocrystal, or a combination thereof) can cover at least a portion of the first semiconductor nanocrystal. The second semiconductor nanocrystal is disposed between the third semiconductor nanocrystal and the first semiconductor nanocrystal. The band gap energy of the second semiconductor nanocrystal can be different from that of the first semiconductor nanocrystal. The band gap energy of the second semiconductor nanocrystal and the band gap energy of the third semiconductor nanocrystal can be greater than the band gap energy of the first semiconductor nanocrystal. The band gap energy of the second semiconductor nanocrystal can be less than the band gap energy of the third semiconductor nanocrystal. The molar ratio between each component in the shell can be adjusted so that the final nanoparticle can exhibit a desired composition and optical properties.
[0075] The size (e.g., thickness or average thickness) of the second semiconductor nanocrystal, the third semiconductor nanocrystal, or the shell can be 0.1 nm or more, 0.3 nm or more, 0.5 nm or more, 0.7 nm or more, 1 nm or more, 1.5 nm or more, 1.7 nm or more, 1.9 nm or more, 2 nm or more, 2.1 nm or more, 2.3 nm or more, 2.5 nm or more, 2.7 nm or more, 2.9 nm or more, 3 nm or more, 3.1 nm or more, 3.3 nm or more, 3.5 nm or more, 3.7 nm or more, or 3.9 nm or more. The size (e.g., thickness or average thickness) of the second semiconductor nanocrystal, the third semiconductor nanocrystal, or the shell can be 5 nm or less, 4.5 nm or less, 4 nm or less, 3.5 nm or less, 3 nm or less, 2.5 nm or less, 2 nm or less, or 1.5 nm or less.
[0076] The semiconductor nanoparticles or the shells may further include a fourth semiconductor nanocrystal containing a zinc chalcogenide or an inorganic layer containing the same, for example as an outermost layer. The zinc chalcogenide may include zinc; and selenium, sulfur, or a combination thereof. The zinc chalcogenide may include ZnSe, ZnSeS, ZnS, or a combination thereof. In one embodiment, the semiconductor nanoparticles may have a core-multi-shell structure including AgInGaS / GaS / ZnS, AgInGaS / AgGaS / ZnS, AgInGaS / ZnGaS / ZnS, AgInGaS / GaS / ZnGaS / ZnS, AgInGaS / AgGaS / ZnGaS / ZnS, or a combination thereof. The thickness of the inorganic layer containing the zinc chalcogenide may be appropriately selected. In one embodiment, the inorganic layer (or outermost layer) may have a thickness in the range of 0.1 nm-5 nm, 0.3 nm-4 nm, 0.5 nm-3.5 nm, 0.7 nm-3 nm, 0.9 nm-2.5 nm, 1 nm-2 nm, 1.5 nm-1.7 nm, or a combination thereof. The outermost layer may have a thickness of 5 nm or less, 4 nm or less, 3.5 nm or less, 3 nm or less, 2.5 nm or less, 2 nm or less, 1.5 nm or less, 1 nm or less, or 0.8 nm or less. The outermost layer may have a thickness of 0.1 nm or more, 0.3 nm or more, 0.5 nm or more, or 0.7 nm or more.
[0077] In one embodiment, the semiconductor nanoparticles can exhibit crystallinity, for example, when determined by appropriate analytical means (e.g., X-ray diffraction analysis, electron microscopy analysis such as High angle annular dark field (HAADF)-scanning transmission electron microscope (STEM) analysis, etc.).
[0078] In one embodiment, the size (or average size) of the semiconductor nanoparticles may be 1 nm or more, 1.5 nm or more, 2 nm or more, 2.5 nm or more, 3 nm or more, 3.5 nm or more, 4 nm or more, 4.5 nm or more, 5 nm or more, 5.5 nm or more, 6 nm or more, 6.5 nm or more, 7 nm or more, 7.5 nm or more, 8 nm or more, 8.5 nm or more, 9 nm or more, 9.5 nm or more, 10 nm or more, or 10.5 nm or more. The size (or average size) of the semiconductor nanoparticles may be 50 nm or less, 48 nm or less, 46 nm or less, 44 nm or less, 42 nm or less, 40 nm or less, 35 nm or less, 30 nm or less, 25 nm or less, 20 nm or less, 18 nm or less, 16 nm or less, 14 nm or less, 12 nm or less, 11 nm or less, 10 nm or less, 8 nm or less, 7 nm or less, 6 nm or less, 5.5 nm or less, or 4 nm or less. In this specification, the size of a particle may be a particle diameter. The size of the particle (if the nanoparticle or first semiconductor nanocrystal is not spherical) can be determined by transmission electron microscopy. For example, the size of a nanoparticle can be the equivalent diameter calculated by converting the two-dimensional area into a circle.
[0079] In one embodiment, the semiconductor nanoparticles contained in the ink composition can be prepared by a method that includes forming the shell (e.g., a second semiconductor nanocrystal and / or a third semiconductor nanocrystal) on the first semiconductor nanocrystal, and the method can further include modifying the surface of the resulting semiconductor nanoparticle with a first organic ligand.
[0080] The first semiconductor nanocrystal or the core can be produced by reacting a precursor required depending on the composition, for example, a silver precursor, an indium precursor, a gallium precursor, and a sulfur precursor in a solution containing an organic ligand and an organic solvent at a predetermined reaction temperature (for example, a temperature range of 20°C to 300°C, 80°C to 295°C, 120°C to 290°C, 200°C to 280°C, or a combination thereof), and separating the precursors. The separation and recovery can be referred to in the manner described below. The method of one embodiment includes heating a solution in which an indium precursor, a gallium precursor, and a sulfur precursor are dissolved in an organic solvent at a predetermined temperature (for example, a temperature of 100°C to 150°C), adding a silver precursor to the heated solution, and reacting at the reaction temperature.
[0081] In one embodiment, forming the shell includes adding a first semiconductor nanocrystal (or a particle comprising the first semiconductor nanocrystal), a metal precursor, a non-metal precursor, or a combination thereof, to a reaction medium, and heating the reaction medium at a reaction temperature. The metal precursor and the non-metal precursor are determined based on the desired shell composition. The metal precursor can include an indium precursor, a gallium precursor, a zinc precursor, or a combination thereof. The non-metal precursor can include a sulfur precursor.
[0082] In one embodiment, forming the shell comprises: The method may include providing a reaction medium comprising a first precursor and optionally an organic ligand in an organic solvent; heating the reaction medium at a first temperature; adding the first semiconductor nanocrystal and a second precursor to the reaction medium; heating the reaction medium at a second temperature and reacting for a first time to form a second semiconductor nanocrystal. One of the first precursor and the second precursor is a gallium precursor and the other is a sulfur precursor. The first temperature may be greater than or equal to 120° C. and less than or equal to 280° C. The second temperature may be greater than or equal to 180° C. and less than or equal to 380° C. The first time may be controlled to obtain a charge balance value for the nanoparticles. The first temperature may be different (lower or higher) than the second temperature. The second temperature may be higher than the first temperature.
[0083] In one embodiment, the first precursor can be a gallium precursor and the second precursor can be a sulfur precursor. In one embodiment, the first precursor can be a sulfur precursor and the second precursor can include a gallium precursor, a zinc precursor, or a combination thereof.
[0084] In one embodiment, the method may further include the steps of: preparing an additional reaction medium comprising an organic ligand and a zinc precursor in an organic solvent; heating the additional reaction medium at a reaction temperature while adding and reacting the formed nanoparticles and a chalcogen precursor to provide an outer layer (e.g., an outermost layer or an inorganic layer) comprising a zinc chalcogenide on the surface of the nanoparticles. The chalcogen precursor may include a sulfur precursor, a selenium precursor, or a combination thereof. The reaction temperature may refer to the items described for the second temperature.
[0085] In preparing the first semiconductor nanocrystal (core), the second semiconductor nanocrystal, the third semiconductor nanocrystal, or the fourth semiconductor nanocrystal, the molar ratio between each precursor can be adjusted to obtain the desired composition of the respective semiconductor nanocrystal or the desired composition of the semiconductor nanoparticle.
[0086] In one embodiment, the content of silver (Ag) precursor per mole of indium can be 0.1 mol or more, 0.3 mol or more, 0.5 mol or more, 0.7 mol or more, 1 mol or more, 1.5 mol or more, 2 mol or more, 2.5 mol or more. In one embodiment, the content of silver precursor per mole of indium can be 10 mol or less, 8 mol or less, 6 mol or less, 4 mol or less, 2 mol or less, 1.2 mol or less, 1 mol or less, or 0.5 mol or less. In one embodiment, the content of gallium precursor per mole of indium can be 0.5 mol or more, 1 mol or more, 1.5 mol or more, 2 mol or more, or 2.5 mol or more. In one embodiment, the content of gallium precursor per mole of indium can be 15 mol or less, 12 mol or less, 10 mol or less, 8 mol or less, 5 mol or less, or 3 mol or less.
[0087] In one embodiment, the amount of sulfur precursor per mole of indium can be 0.5 moles or more, 1 mole or more, 1.5 moles or more, 2 moles or more, 2.5 moles or more, 3 moles or more, 3.5 moles or more, 4 moles or more, or 4.5 moles or more. In one embodiment, the amount of sulfur precursor per mole of indium can be 20 moles or less, 15 moles or less, 10 moles or less, 8 moles or less, 6 moles or less, 4 moles or less, or 2 moles or less.
[0088] The difference between the first temperature and the second temperature can be 10° C. or more, 20° C. or more, 30° C. or more, 40° C. or more, 50° C. or more, 60° C. or more, 70° C. or more, 80° C. or more, 90° C. or more, or 100° C. The difference between the first temperature and the second temperature can be 200° C. or less, 190° C. or less, 180° C. or less, 170° C. or less, 160° C. or less, 150° C. or less, 140° C. or less, 130° C. or less, 120° C. or less, 110° C. or less, 100° C. or less, 90° C. or less, 80° C. or less, 70° C. or less, 60° C. or less, 50° C. or less, 40° C. or less, 30° C. or less, or 20° C. or less.
[0089] The first temperature can be 120° C. or more, 200° C. or more, 210° C. or more, 220° C. or more, 230° C. or more, 240° C. or more, or 250° C. or more. The first temperature can be 280° C. or less, 275° C. or less, 270° C. or less, 265° C. or less, 260° C. or less, 255° C. or less, 250° C. or less, 240° C. or less, 230° C. or less, 220° C. or less, 210° C. or less, 200° C. or less, 190° C. or less, 180° C. or less, 170° C. or less, 160° C. or less, or 150° C. or less.
[0090] The second temperature can be 140°C or more, 150°C or more, 160°C or more, 170°C or more, 180°C or more, 190°C or more, 200°C or more, 210°C or more, 220°C or more, 230°C or more, 245°C or more, 250°C or more, 255°C or more, 260°C or more, 265°C or more, 270°C or more, 275°C or more, 280°C or more, 285°C or more, 290°C or more, 295°C or more, 300°C or more, 305°C or more, 310°C or more, 315°C or more, 320°C or more, 330°C or more, 335°C or more, 340°C or more, or 345°C or more. The second temperature can be 380°C or less, 375°C or less, 370°C or less, 365°C or less, 360°C or less, 355°C or less, 350°C or less, 340°C or less, 330°C or less, 320°C or less, 310°C or less, 300°C or less, 290°C or less, 280°C or less, 270°C or less, 260°C or less, or 250°C or less.
[0091] The first time period can be controlled to obtain a charge balance value for the nanoparticles. Without wishing to be bound by any particular theory, it is believed that in one embodiment of the method, the first and second temperatures and the first time period can be adjusted to effectively suppress the generation of by-products (e.g., gallium oxide) during the formation of nanoparticles, thereby allowing the nanoparticles to exhibit the above-mentioned charge balance value (and optionally the molar ratio between each component described herein).
[0092] In one embodiment, the first time may be in the range of 1 minute to 240 minutes, 5 minutes to 200 minutes, 10 minutes to 3 hours, 20 minutes to 150 minutes, 30 minutes to 100 minutes, or a combination thereof. The first time may be selected taking into consideration the type of precursor, the reaction temperature, the desired composition of the final particles, and the like. In one embodiment, the second temperature is in a relatively high temperature range (e.g., 220°C or more, 240°C or more, 260°C or more, 280°C or more, 285°C to 340°C, or 290°C to 330°C), and the first time may be 1 minute or more, 5 minutes or more, 10 minutes or more, 15 minutes or more, 20 minutes or more, or 25 minutes or more and 2 hours or less, 90 minutes or less, 80 minutes or less, 70 minutes or less, 60 minutes or less, 50 minutes or less, 45 minutes or less, 40 minutes or less, 35 minutes or less, 30 minutes or less, 25 minutes or less, 20 minutes or less, 15 minutes or less, or 12 minutes or less. In one embodiment, the second temperature is within a relatively low temperature range (e.g., less than 290° C., 280° C. or less, 270° C. or less, 260° C. or less, 250° C. or less, 240° C. or less, 230° C. or less, 220° C. or less, or 210° C. or less), and the first reaction time can be 30 minutes or more, 35 minutes or more and 40 minutes or more, 45 minutes or more, 50 minutes or more, 55 minutes or more, 60 minutes or more, 65 minutes or more, 70 minutes or more, 75 minutes or more, or 80 minutes or more.
[0093] The type of silver precursor is not particularly limited and can be appropriately selected. The silver precursor can include silver powder, alkylated silver compounds, silver alkoxides, silver carboxylates, silver acetylacetonates, silver nitrates, silver sulfates, silver halides, silver cyanides, silver hydroxides, silver oxides, silver peroxides, silver carbonates, or combinations thereof. The silver precursor can include silver nitrates, silver acetates, silver acetylacetonates, silver chlorides, silver bromides, silver iodides, or combinations thereof.
[0094] The type of indium precursor is not particularly limited and can be appropriately selected. The indium precursor can be indium powder, alkylated indium compound, indium alkoxide, indium carboxylate, indium nitrate, indium percolate, indium sulfate, indium acetylacetonate, indium halide, indium cyanide, indium hydroxide, indium oxide, indium peroxide, indium carbonate, indium acetate, or a combination thereof. The indium precursor can include indium carboxylate such as indium oleate, indium myristate, indium acetate, indium hydroxide, indium chloride, indium bromide, and indium iodide.
[0095] The type of gallium precursor is not particularly limited and can be appropriately selected.The gallium precursor can be gallium powder, alkylated gallium compounds, gallium alkoxides, gallium carboxylates, gallium nitrates, gallium percolates, gallium sulfates, gallium acetylacetonates, gallium halides, gallium cyanides, gallium hydroxides, gallium oxides, gallium peroxides, gallium carbonates, gallium chlorides, gallium bromides, gallium iodides, or combinations thereof.The gallium precursor can include gallium chlorides, gallium iodides, gallium bromides, gallium acetates, gallium acetylacetonates, gallium oleates, gallium palmitates, gallium stearates, gallium myristates, gallium hydroxides, or combinations thereof.
[0096] The type of sulfur precursor is not particularly limited and can be appropriately selected. The sulfur precursor may be an organic solvent dispersion or reaction product of sulfur (e.g., sulfur-oleylamine (S-oleylamine), sulfur-dodecylamine (S-dodecylamine), sulfur-octadecene (S-ODE), trioctylphosphine-sulfide (S-TOP), tributylphosphine-sulfide (S-TBP), triphenylphosphine-sulfide (S-TPP), sulfur-trioctylamine (S-TOA), trimethylsilyl alkyl sulfide, bis(trimethylsilyl) sulfide, mercaptopropylsilane, ammonium sulfide, sodium sulfide, C1-30 thiol compounds (e.g., α-toluenethiol, octanethiol, dodecanethiol, octadecenethiol, etc.), isothiocyanate compounds (e.g., cyclohexyl isothiocyanate), alkylene trithiocarbonates (e.g., ethylene trithiocarbonate, etc.), trithiocarbonate), allyl mercaptan, thiourea compounds (e.g., thiourea, dialkylthiourea, phenylthiourea), or combinations thereof.
[0097] When present, the selenium precursor may include trioctylphosphine selenide (Se-TOP), tributylphosphine selenide (Se-TBP), triphenylphosphine selenide (Se-TPP), or combinations thereof.
[0098] The type of zinc precursor is not particularly limited and can be appropriately selected.For example, the zinc precursor can be Zn metal powder, alkylated Zn compound, Zn alkoxide, Zn carboxylate, Zn nitrate, Zn percolate, Zn sulfate, Zn acetylacetonate, Zn halide, Zn cyanide, Zn hydroxide, Zn oxide, Zn peroxide, or a combination thereof.The zinc precursor can be dimethyl zinc, diethyl zinc, zinc acetate, zinc acetylacetonate, zinc iodide, zinc bromide, zinc chloride, zinc fluoride, zinc carbonate, zinc cyanide, zinc nitrate, zinc oxide, zinc peroxide, zinc perchlorate, zinc sulfate, etc.
[0099] The organic ligand is RCOOH, RNH 2 , R 2 N.H., R. 3 N, R.S.H., R.H. 2 P.O., R. 2 H.P.O., R. 3 P.O., R.H. 2 P, R 2 H.P., R. 3 P, ROH, RCOOR', RPO(OH) 2 , R.H.P.O.H., R. 2POOH (wherein R and R' each independently may comprise a substituted or unsubstituted C1-C40 (or C3-C24) aliphatic hydrocarbon (e.g., alkyl group, alkenyl group, alkynyl group), or a substituted or unsubstituted C6-C40 (or C6-C24) aromatic hydrocarbon (e.g., C6-C20 aryl group), or a combination thereof. The organic ligand may be a ligand that is bound to the surface of the prepared nanoparticles (so-called native ligand). The native ligand may be introduced during the preparation of semiconductor nanoparticles such as quantum dots, and may coordinate the surface of the semiconductor nanoparticles.The organic ligands include methanethiol, ethanethiol, propanethiol, butanethiol, pentanethiol, hexanethiol, heptanethiol, octanethiol, nonanethiol, decanethiol, dodecanethiol, hexadecanethiol, octadecanethiol, benzylthiol; methylamine, ethylamine, propylamine, butylamine, pentylamine, hexylamine, octylamine, dodecylamine, hexadecylamine, octadecylamine, oleylamine, dimethylamine, diethylamine, dipropylamine; methanoic acid, ethanoic acid, propanoic acid, butanoic acid, pentanoic acid, hexanoic acid, heptanoic acid, octanoic acid, dodecanoic acid, hexadecanoic acid, octadecanoic acid, oleic acid, benzoic acid; substituted or unsubstituted methylphosphines (e.g., trimethylphosphine, methyldiphenylphosphine, etc.), substituted or unsubstituted ethylphosphines (e.g., triethylphosphine, phosphines such as sphines, ethyldiphenylphosphine, etc.), substituted or unsubstituted propylphosphine, substituted or unsubstituted butylphosphine, substituted or unsubstituted pentylphosphine, substituted or unsubstituted octylphosphine (e.g., trioctylphosphine (TOP)); phosphine oxides such as substituted or unsubstituted methylphosphine oxide (e.g., trimethylphosphine oxide, methyldiphenylphosphine oxide, etc.), substituted or unsubstituted ethylphosphine oxide (e.g., triethylphosphine oxide, ethyldiphenylphosphine oxide, etc.), substituted or unsubstituted propylphosphine oxide, substituted or unsubstituted butylphosphine oxide, substituted or unsubstituted octylphosphine oxide (e.g., trioctylphosphine oxide (TOPO)); diphenylphosphine, triphenylphosphine compounds, or oxide compounds thereof; phosphonic acids (phosphonic Examples of the phosphinic acid include, but are not limited to, C5 to C20 alkyl phosphinic acids such as hexyl phosphinic acid, octyl phosphinic acid, dodecane phosphinic acid, tetradecane phosphinic acid, hexadecane phosphinic acid, and octadecane phosphinic acid, and C5 to C20 alkyl phosphonic acids.The organic ligands may be used alone or in mixtures of two or more.
[0100] The organic solvent is selected from the group consisting of amine solvents, nitrogen-containing heterocyclic compounds such as pyridine; C6 to C40 aliphatic hydrocarbons (e.g., alkanes, alkenes, alkynes, etc.) such as hexadecane, octadecane, octadecene, and squalane; C6 to C30 aromatic hydrocarbons such as phenyldodecane, phenyltetradecane, and phenylhexadecane; phosphines substituted with C6 to C22 alkyl groups such as trioctylphosphine; phosphine oxides substituted with C6 to C22 alkyl groups such as trioctylphosphine oxide; C12 to C22 aromatic ethers such as phenyl ether and benzyl ether, and combinations thereof. The amine solvent can be a compound having one or more (e.g., two or three) C1-50, C2-45, C3-40, C4-35, C5-30, C6-25, C7-20, C8-15, or C6-22 aliphatic hydrocarbon groups (alkyl, alkenyl, or alkynyl groups). In one embodiment, the amine solvent can include a C6-22 primary amine, such as hexadecylamine, oleylamine, etc.; a C6-22 secondary amine, such as dioctylamine, etc.; a C6-22 tertiary amine, such as trioctylamine, etc.; or a combination thereof.
[0101] The content of the organic ligand and each precursor in the reaction medium can be appropriately selected taking into consideration the type of solvent, the type of the organic ligand and each precursor, the desired particle size and composition, etc. The molar ratio between each precursor can be appropriately selected taking into consideration the desired molar ratio in the final nanoparticles, the reactivity between each precursor, etc.
[0102] The method of adding each precursor is not particularly limited, and each precursor may be added in one or more portions, or in two or more portions up to ten portions. Each precursor may be added simultaneously or sequentially. The reaction may be performed in an inert gas atmosphere, in air, or in a vacuum, but is not limited thereto.
[0103] After the reaction is completed, a nonsolvent is added to the final reaction solution, and the nanoparticles (e.g., to which the organic ligand is coordinated) are separated (e.g., precipitated). The nonsolvent may be a polar solvent that is miscible with the solvent used in the reaction but cannot disperse the nanocrystals. The nonsolvent may be determined according to the solvent used in the reaction, and may include, for example, acetone, ethanol, butanol, isopropanol, ethanediol, water, tetrahydrofuran (THF), dimethylsulfoxide (DMSO), diethylether, formaldehyde, acetaldehyde, a solvent having a solubility parameter similar to the solvents listed above, or a combination thereof. Separation may be performed by centrifugation, precipitation, chromatography, or distillation. The separated nanocrystals may be washed by adding to a washing solvent as necessary. The washing solvent is not particularly limited, and a solvent having a solubility parameter similar to the organic solvent or the ligand may be used. The non-solvent or wash solvent may include, but is not limited to, alcohol; alkane solvents such as hexane, heptane, octane, etc.; chloroform; aromatic solvents such as toluene, benzene, etc.; or combinations thereof.
[0104] The prepared semiconductor nanoparticles (before surface modification with the first organic ligand) may contain the compound used in the preparation method (e.g., an organic amine such as oleylamine) as a native ligand and are dispersed in a dispersion solvent. The dispersion solvent may include substituted or unsubstituted C1-C40 aliphatic hydrocarbons, substituted or unsubstituted C6-C40 aromatic hydrocarbons, or combinations thereof.
[0105] The present inventors have confirmed that semiconductor nanoparticles based on 11-13-16 group compounds containing native ligands may have significantly reduced luminescence properties (e.g., luminescence properties) when mixed with components (e.g., polymerizable monomers) for forming an inkjet ink composition or when prepared as a composite. In display devices (e.g., TVs and Watches, VR, AR) containing micro LEDs, an increased light conversion rate (e.g., luminescence efficiency) is desirable. Surprisingly, the present inventors have confirmed that the luminescence properties in the semiconductor nanoparticle composite may be significantly changed depending on the ligand of the semiconductor nanoparticles or a combination thereof, the bond between the ink matrix and the ligand, dispersibility, etc.
[0106] As confirmed by the present inventors, such organic amines can control the reactivity of the precursors, but are difficult to provide sufficient dispersibility for forming, for example, a colloidal ink composition (e.g., for an inkjet printing process or without a separate volatile organic solvent). Without wishing to be bound by a particular theory, it is believed that this is because the organic amine compound of the organic ligand makes the surface of the semiconductor nanoparticles non-polar, and therefore, while it can be dispersed in a dispersion solvent such as an alkane or toluene, it is difficult to disperse in a vehicle that shows polarity, such as the monomer in the ink composition.
[0107] In order to eliminate such dispersibility, it is conceivable to replace the original ligand of the semiconductor nanoparticles with an organic ligand (e.g., of a polymer type) that exhibits polarity (e.g., containing an alkylene oxide group or an alkylene ester residue). However, the present inventors have confirmed that, in the case of such ligands, it is difficult to provide the semiconductor nanoparticles with the desired dispersibility, it is difficult to provide the desired level of coatability, and there is also a limit to the improvement of the optical properties of the semiconductor nanoparticles in the ink composition.
[0108] The present inventors have surprisingly found that semiconductor nanoparticles containing the first organic ligand as described herein can stably provide a desired dispersibility in an ink composition, and therefore the content of the semiconductor nanoparticles in the ink composition can be adjusted (e.g., increased) to a desired level. In addition, the inventors have found that an ink composition according to an embodiment can prevent damage to the optical properties of semiconductor nanoparticles due to heat that may accompany a pattern formation process while exhibiting improved coating properties in an inkjet printing process, or can exhibit further improved luminescence properties after such heat treatment. Without wishing to be bound by a particular theory, it is believed that the fluorine-substituted aromatic chemical structure contained in the first organic ligand can reduce the surface energy of the composition, thereby exhibiting improved coating properties. In addition, the steric hindrance provided by the chemical structure of the ligand can provide an improved level of passivation to the semiconductor nanoparticles even when the ligand compound has a relatively low molecular weight, and the luminescence properties of the semiconductor nanoparticles are significantly improved, and thus it is believed that the resulting composition or composite can effectively prevent a decrease in light efficiency even after heat treatment.
[0109] In one embodiment, the semiconductor nanoparticles are ligand-exchanged or surface-modified to include a first organic ligand on the surface. Thus, in one embodiment, the ink composition may include semiconductor nanoparticles and a first organic ligand. The first organic ligand may coordinate to the surface of the semiconductor nanoparticles. In one embodiment, at least a portion of the native ligand present in the synthesized semiconductor nanoparticles may be replaced with the first organic ligand by ligand exchange. In one embodiment, the ligand-exchanged semiconductor nanoparticles may include both the native ligand and the first organic ligand on the surface.
[0110] One embodiment relates to a semiconductor nanoparticle having a first organic ligand on its surface. The details of the semiconductor nanoparticle and the organic ligand are as described herein. In one embodiment, the ink composition includes a semiconductor nanoparticle having a first organic ligand on its surface, and the ink composition including the first organic ligand can produce a pattern with improved stability, and the produced composite can exhibit desired luminescence properties.
[0111] The first organic ligand is represented by Formula 1: [Chemical formula 1] AL-Ar In the above formula, A is a functional group configured to interact with (e.g., bind to) the surface of the semiconductor nanoparticle; L includes a single bond, a substituted or unsubstituted aliphatic hydrocarbon group having 1 to 40 carbon atoms (or 2 to 20 carbon atoms) (e.g., an alkylene group, an alkenylene group, or an alkynylene group), a substituted or unsubstituted aromatic hydrocarbon group having 6 to 40 carbon atoms (or 6 to 20 carbon atoms), a substituted or unsubstituted alicyclic hydrocarbon group having 3 to 40 carbon atoms (or 3 to 20 carbon atoms), -CO-, -O-, -COO-, -S-, -SO-, -NHCO-, -NH-, or a combination thereof (e.g., residues of two or more of the above-mentioned groups), Ar is a fluorine-containing aromatic group having 6 to 40 carbon atoms (or 6 to 20 carbon atoms) (e.g., one or more fluorine atoms or one or more fluorine-containing organic groups, such as the residues denoted herein as "flu"). The aromatic group may further include additional substituents other than fluorine. The fluorine-containing aromatic group may be a substituted aromatic hydrocarbon group having 6 to 40 carbon atoms that contains, or is substituted with, one or more fluorine atoms or fluorine-containing groups (e.g., the residue represented by flu in Chemical Formula 2-1) in place of hydrogen atoms.
[0112] The first organic ligand may include a compound represented by Formula 2-1. [ka] In the above formula, A is a functional group configured to interact with (e.g., bind to) the surface of the semiconductor nanoparticle; L includes a single bond, a substituted or unsubstituted aliphatic hydrocarbon group having 1 to 40 carbon atoms (or 2 to 20 carbon atoms (e.g., an alkylene group such as methylene, ethylene, propylene, etc., an alkenylene group, or an alkynylene group) having 1 to 5 carbon atoms or 2 to 3 carbon atoms), a substituted or unsubstituted aromatic hydrocarbon group having 6 to 40 carbon atoms (or 6 to 20 carbon atoms (e.g., phenylene), a substituted or unsubstituted alicyclic hydrocarbon group having 3 to 40 carbon atoms (or 3 to 20 carbon atoms), -CO-, -O-, -COO-, -S-, -SO-, -NHCO-, -NH-, or a combination thereof; flu includes a fluoro group (-F), a fluorine-substituted aliphatic hydrocarbon group having 1 to 30 carbon atoms (e.g., 2 to 20 carbon atoms, 3 to 10 carbon atoms) (e.g., a fluoroalkyl group, a fluoroalkenyl group, a fluoroalkynyl group), a fluorine-substituted aromatic hydrocarbon group having 6 to 20 carbon atoms (e.g., a fluoroaryl group such as a fluorophenyl group), or a combination thereof; n is 1, 2, 3, 4, or 5.
[0113] The fluoroalkyl group, the fluoroalkenyl group, the fluoroalkynyl group, or the fluoroaryl group may be a monofluoro functional group. The fluoroalkyl group, the fluoroalkenyl group, the fluoroalkynyl group, or the fluoroaryl group may have 2 or more, 3 or more, 4 or more, 5 or more, 6 or more, 7 or more, 8 or more, 9 or more, or 10 or more fluorines. The fluoroalkyl group, the fluoroalkenyl group, the fluoroalkynyl group, or the fluoroaryl group may contain 50 or less, 40 or less, 30 or less, 20 or less, 15 or less, 9 or less, or 3 or less fluorine atoms. The fluoroalkyl group, the fluoroalkenyl group, the fluoroalkynyl group, or the fluoroaryl group may be a perfluoro group or a polyfluoro group. For example, the fluoroalkyl group, the fluoroalkenyl group, the fluoroalkynyl group, or the fluoroaryl group can be a perfluoroalkyl group, a perfluoroalkenyl group, a perfluoroalkynyl group, or a perfluoroaryl group, respectively.
[0114] In the definition of L in the above formula, the substituted or unsubstituted aliphatic hydrocarbon group having 1 to 40 (2 to 20) carbon atoms may have one or more methylenes substituted with -CO-, -O-, -COO-, -S-, -SO-, -NHCO-, -NH-, or a combination thereof. In the above formula, L may be an alkylene or alkenylene group of C1-3, C2-4, C5-6, or a combination thereof (e.g., methylene, ethylene, or propylene), and optionally one or more methylenes of the alkylene or alkenylene group may be substituted with -CO-, -O-, -COO-, -S-, -SO-, -NHCO-, -NH-, or a combination thereof.
[0115] In the above formula, A is a carboxyl group (-COOH), an amine group (-NRH), a thiol group (-SH), a hydroxyl group (-OH), or -P(O)(OH). 2 , -PR 2 , or -P(O)R2 or a residue derived therefrom (for example, a group obtained by removing H from each residue, for example, COO-, NR-, S-, O-, -P(O)(OH)(O - ), where R can be hydrogen, an aliphatic hydrocarbon having 1 to 30 carbon atoms, an aromatic hydrocarbon having 6 to 30 carbon atoms, or a combination thereof.
[0116] The first organic ligand may be free of acrylate residues.The first organic ligand may be free of amine or amide groups. The first organic ligand may further include a carboxy group or a carboxylate group.The first organic ligand may further include a thiol group or a thiolate group.
[0117] The first organic ligand can include a compound represented by formula 2-2 or a compound derived therefrom (e.g., a carboxylate compound): [ka] In the above formula, R is independently hydrogen or a substituted or unsubstituted alkyl group having 1 to 10 carbon atoms; 1 is a site for binding to hydrogen or a semiconductor nanoparticle; m is 0 or an integer ranging from 1 to 10, 2 to 8, 3 to 6, 4 to 5, 7 to 9, or a combination thereof; n 2 is 1-20, 2-15, 3-10, or 4-8, for example, 1, 2, 3, 4, or 5, and Ar is a group containing an aromatic ring having 6 to 50 carbon atoms or 12 to 40 carbon atoms (for example, a phenylene group, a naphthylene group, an anthrylene group, or a phenanthrylene group). 2 may be a condensed group of an alicyclic and an aromatic group.
[0118] The first organic ligand may include a compound represented by the following formula: [ka] In the above formula, R, m, A 1 , n 2 is as defined above.
[0119] The first organic ligand is attached to a surface of the semiconductor nanoparticle. The first organic ligand may include fluoronaphthalene acid, fluorobenzoic acid, fluorophenyl carboxylic acid compounds (e.g., fluorophenyl acetic acid, fluorophenyl propionic acid, fluorophenyl butyric acid, fluorophenyl pentanoic acid, fluorophenyl hexanoic acid, etc.), fluoronaphthyl carboxylic acid compounds, fluoroanthracenyl carboxylic acid compounds, phenyl carboxylic acid compounds substituted with a fluoroalkyl group, phenyl carboxylic acid compounds substituted with a fluoroalkenyl group, phenyl carboxylic acid compounds substituted with a fluoroalkynyl group, fluorophenyl carboxylic acid compounds substituted with a fluorophenyl group, or combinations thereof. In the above description, "fluoro" includes fluoro or perfluoro. For example, the description "fluorophenyl" includes not only "fluorophenyl" but also "perfluorophenyl".
[0120] The first organic ligand can be a compound having 100 or less, 50 or less, 30 or less, or 20 or less carbon atoms and / or 2 or more, 3 or more, 5 or more, 7 or more, 9 or more, 10 or more, or 15 or more carbon atoms. The first organic ligand can include a polymeric compound, a non-polymeric compound, or a combination thereof.
[0121] The first organic ligand may have a molecular weight of 500 g / mol or less, 450 g / mol or less, 400 g / mol or less, 350 g / mol or less, 300 g / mol or less, 250 g / mol or less, 200 g / mol or less, or 180 g / mol or less. The first organic ligand may have a molecular weight of 50 g / mol or more, 80 g / mol or more, 90 g / mol or more, 100 g / mol or more, 120 g / mol or more, or 150 g / mol or more.
[0122] In one embodiment, ligand exchange can include contacting the semiconductor nanoparticles having the nascent ligand with a first organic ligand, for example in an organic solvent. The contacting can include adding the first organic ligand to the organic solvent dispersion of the semiconductor nanoparticles having the nascent ligand. The organic solvent dispersion can be prepared by dispersing the semiconductor nanoparticles (either before ligand exchange or with the nascent ligand) in an organic solvent.
[0123] In one embodiment, the residue bound to the semiconductor nanoparticle in the native ligand and the functional group of the first organic ligand may be different. In one embodiment, the native ligand may be an amine compound, and the first organic ligand may be a carboxylic acid compound. The temperature and time for the ligand exchange may be appropriately selected. For example, the ligand exchange may be performed at a temperature ranging from 10°C to 100°C, 20°C to 80°C, 25°C to 50°C, 30°C to 40°C, or a combination thereof. The ligand exchange may be performed at room temperature (e.g., 20-30°C). For example, the reaction time for the ligand exchange may be 5 minutes or more, 30 minutes or more, 1 hour or more, or 12 hours or more. The reaction time for the ligand exchange may be 10 days or less, 7 days or less, 5 days or less, 50 hours or less, 40 hours or less, 30 hours or less, 20 hours or less, 15 hours or less, 10 hours or less, 8 hours or less, 5 hours or less, 4 hours or less, 3 hours or less, or 1 hour or less.
[0124] In one embodiment, the nanocrystalline particles containing the native ligands can be treated with a zinc salt prior to the ligand exchange reaction, and then the ligand exchange reaction can be carried out, for example, in the presence of additional zinc salt compounds. In one embodiment of the method, the ligand exchange can be carried out in the presence of additional zinc salt compounds.
[0125] The zinc salt treatment can be carried out by contacting the semiconductor nanoparticles (either before ligand exchange or with the native ligands) with a zinc salt compound in an organic solvent.
[0126] The organic solvent can be appropriately selected in consideration of the types of organic ligand compound, natural ligand, and zinc salt compound. The organic solvent can be an aliphatic hydrocarbon (e.g., alkane, alkene, alkyne) solvent having 6 to 40 carbon atoms such as octane, hexane, heptane, etc.; an aromatic hydrocarbon solvent having 6 to 30 carbon atoms such as toluene, xylene, etc.; or a combination thereof.
[0127] The zinc salt compound or the additional zinc salt compound may include a zinc fatty acid ester compound having 8 to 50 carbon atoms (e.g., zinc oleate, zinc stearate, zinc myristate, etc.), a zinc halide (e.g., zinc chloride, zinc bromide, zinc iodide, zinc fluoride, etc.), or a combination thereof. The zinc salt compound for the zinc salt treatment and the zinc salt compound utilized during the ligand exchange may be the same or different.
[0128] The zinc salt treatment temperature or the ligand exchange reaction temperature may be 20° C. or more, 30° C. or more, 40° C. or more, 45° C. or more, or 50° C. or more. The zinc salt treatment temperature or the ligand exchange reaction temperature may be 150° C. or less, 100° C. or less, or 80° C. or less, 60° C. or less, 55° C. or less, or 45° C. or less. The zinc salt treatment time or ligand exchange reaction time may be 50 minutes or more, 1 hour or more, 90 minutes or more, 100 minutes or more, 2 hours or more, 3 hours or more, and 5 days or less, 4 days or less, 3 days or less, 2 days or less, 1 day or less, or 12 hours or less.
[0129] The amount of the zinc salt compound used can be appropriately selected taking into consideration the type of compound and the type of ligand compound, the desired degree of substitution, etc. The amount of the zinc salt compound used during the zinc salt treatment can be 0.01 moles or more, 0.1 moles or more, 0.5 moles or more, 1 mole or more, 5 moles or more, 10 moles or more, 100 moles or more, 500 moles or more, 1000 moles or more, 5000 moles or more, 10,000 moles or more, 15,000 moles or more, 20,000 moles or more, and 200,000 moles or less, 150,000 moles or less, 100,000 moles or less, 50,000 moles or less, 30,000 moles or less, 20,000 moles or less, 10,000 moles or less, 5000 moles or less, 1000 moles or less, 50 moles or less, 1 mole or less, 5 moles or less, 1 mole or less, or 0.5 moles or less. The amount of the zinc salt compound used in the ligand exchange may be 0.001 mol or more, 0.005 mol or more, 0.01 mol or more, 0.03 mol or more, 0.1 mol or more, 0.5 mol or more, 1 mol or more, and 5 mol or less, 1 mol or less, or 0.5 mol or less, relative to 1 mol of the organic ligand used in the ligand exchange. In the ligand exchange, the amount of the first organic ligand used may be 10 moles or more, 50 moles or more, 100 moles or more, 300 moles or more, 400 moles or more, 500 moles or more, 600 moles or more, 700 moles or more, 1000 moles or more, 1500 moles or more, 2000 moles or more, 2500 moles or more, 3000 moles or more, 3500 moles or more, 4000 moles or more, 4500 moles or more, 5000 moles or more, 5500 moles or more, 6000 moles or more, 6500 moles or more, 7000 moles or more, 7500 moles or more, 8000 moles or more, 8500 moles or more, 9000 moles or more, 10,000 moles or more, 12,000 moles or more, 15,000 moles or more, 17,000 moles or more, 19,000 moles or more, or 19,500 moles or more and 20,000 moles or less based on the content (1 mole) of the semiconductor nanoparticles.
[0130] In one embodiment, after ligand exchange, a non-solvent (e.g., an alkane solvent such as hexane or octane, or an aromatic solvent such as toluene) can be added to the reaction solution containing the semiconductor nanoparticles to promote precipitation. The ligand-exchanged semiconductor nanoparticles can exhibit dispersion properties that differ from those of the native ligand. The ligand-exchanged semiconductor nanoparticles can be well dispersed in a liquid vehicle for an ink composition (e.g., a monomer described herein). In one embodiment, the semiconductor nanoparticles or the semiconductor nanoparticle-polymer composites (e.g., having a surface modified with a first organic ligand) have further enhanced physical properties and are configured to emit a desired light (e.g., a first light).
[0131] The first light may be green light or red light. The semiconductor nanoparticles or the first light may have an emission peak wavelength of 490 nm or more, 500 nm or more, 505 nm or more, 510 nm or more, 515 nm or more, 520 nm or more, 525 nm or more, 530 nm or more, 535 nm or more, 540 nm or more, 545 nm or more, 550 nm or more, 555 nm or more, 560 nm or more, 565 nm or more, 570 nm or more, 575 nm or more, 580 nm or more, 585 nm or more, 590 nm or more, or 600 nm or more. The maximum emission peak wavelength of the first light may be 660nm or less, 650nm or less, 640nm or less, 630nm or less, 620nm or less, 610nm or less, 600nm or less, 595nm or less, 590nm or less, 580nm or less, 575nm or less, 570nm or less, 565nm or less, 560nm or less, 555nm or less, 550nm or less, 545nm or less, 540nm or less, 535nm or less, 530nm or less, 525nm or less, 520nm or less, or 515nm or less. The emission peak wavelength of the green light may be 500nm or more and 580nm or less. The emission peak wavelength of the red light may be 600nm or more and 650nm or less.
[0132] The first light may have a half width of 5 nm or more, 10 nm or more, 15 nm or more, 20 nm or more, 25 nm or more, or 30 nm or more. The half width may be 70 nm or less, 65 nm or less, 60 nm or less, 55 nm or less, 50 nm or less, 45 nm or less, 40 nm or less, 38 nm or less, 36 nm or less, 35 nm or less, 34 nm or less, 33 nm or less, 32 nm or less, 31 nm or less, 30 nm or less, 29 nm or less, 28 nm or less, 27 nm or less, 26 nm or less, or 25 nm or less.
[0133] The semiconductor nanoparticles may exhibit a quantum yield of 50% or more. The quantum yield may be an absolute quantum yield. The quantum yield may be 55% or more, 60% or more, 65% or more, 70% or more, 75% or more, 80% or more, 85% or more, 90% or more, or 95% or more. The quantum yield may be 100% or less, 99.5% or less, 99% or less, 98% or less, or 97% or less. The first light may include band edge emission.
[0134] In one embodiment, the molar ratio of zinc in the semiconductor nanoparticles may be 0.8 or less, 0.3 or less, or 0.25 or less based on the chalcogen element (e.g., sulfur).The molar ratio of zinc in the semiconductor nanoparticles may be 0.01 or more, 0.05 or more based on the chalcogen element (e.g., sulfur).
[0135] In the semiconductor nanoparticles, the molar ratio of zinc to the sum of zinc, indium, gallium, and silver (Zn / (In+Ga+Ag+Zn)), hereinafter referred to as relative zinc molar ratio) may be 0.25 or more, 0.3 or more, 0.35 or more, 0.4 or more, 0.45 or more, 0.5 or more, and 10 or less, 9 or less, 8 or less, 7 or less, 6 or less, 5 or less, 4 or less, 3 or less, 2 or less, 1 or less, 0.9 or less, 0.8 or less, 0.7 or less, 0.65 or less, 0.6 or less, 0.55 or less, 0.5 or less, or 0.48 or less.
[0136] In one embodiment of the semiconductor nanoparticles, the molar ratio of zinc (Zn) to silver (Ag) (Zn / Ag) can be 0.3 or more, 0.35 or more, 0.4 or more, 0.45 or more, 0.5 or more, 0.55 or more, 0.6 or more, 0.65 or more, 0.7 or more, 0.75 or more, 0.8 or more, 0.85 or more, 0.9 or more, 0.95 or more, 1 or more, 1.2 or more, 1.4 or more, 1.6 or more, 1.7 or more, 1.9 or more, 2 or more, 2.5 or more, 3 or more, 3.5 or more, or 4 or more. In one embodiment of the semiconductor nanoparticles, the molar ratio of zinc (Zn) to silver (Ag) (Zn / Ag) can be 5 or less, 4.7 or less, 4.4 or less, 4.1 or less, 3.9 or less, 3.7 or less, 3.5 or less, 3 or less, 2.7 or less, 2.6 or less, or 2.3 or less.
[0137] In one embodiment, the semiconductor nanoparticles can have a molar ratio of zinc (Zn) to indium (Zn / In) of 0.1 or more, 0.3 or more, 0.5 or more, 0.7 or more, 0.9 or more, 1.1 or more, 1.3 or more, 1.5 or more, 1.7 or more, 1.9 or more, 2.1 or more, 2.3 or more, 2.5 or more, 2.7 or more, 2.9 or more, or 3 or more. In one embodiment, the semiconductor nanoparticles can have a molar ratio of zinc (Zn) to indium (Ag) (Zn / In) of 20 or less, 18 or less, 16 or less, 14 or less, 12 or less, 10 or less, 8 or less, 6 or less, 5 or less, 4.5 or less, 4 or less, 3.5 or less, 2 or less, or 1.6 or less.
[0138] In one embodiment, the semiconductor nanoparticles can have a molar ratio of zinc (Zn) to gallium (Zn / Ga) of 0.1 or more, 0.2 or more, 0.3 or more, 0.35 or more, 0.4 or more, 0.45 or more, 0.5 or more, or 1 or more. In one embodiment, the semiconductor nanoparticles can have a molar ratio of zinc (Zn) to gallium (Zn / Ga) of 3 or less, 2.5 or less, 2 or less, 1.9 or less, 1.7 or less, 1.5 or less, 1.4 or less, 1.2 or less, 1.1 or less, 0.9 or less, 0.8 or less, 0.7 or less, 0.6 or less, or 0.49 or less.
[0139] In one embodiment of the semiconductor nanoparticles, the molar ratio of zinc (Zn) to the sum of gallium, silver, and indium (Zn / (Ga+In+Ag)) can be 0.05 or more, 0.1 or more, 0.2 or more, 0.25 or more, 0.3 or more, 0.35 or more, 0.4 or more, 0.5 or more, 0.6 or more, 0.7 or more, 0.8 or more, 0.9 or more, or even 1. In one embodiment of the semiconductor nanoparticles, the molar ratio of zinc (Zn) to the sum of gallium, silver, and indium (Zn / (Ga+In+Ag)) can be 3 or less, 2.5 or less, 2 or less, 1.7 or less, 1.4 or less, 1.1 or less, 0.9 or less, 0.7 or less, 0.5 or less, or 0.45 or less.
[0140] The semiconductor nanoparticles may have a charge balance value of 0.8 or more and 1.8 or less, or 1.6 or less, or 1.5 or less, as represented by the following formula: charge balance value={[Ag]+3x([In]+[Ga])+2x[Zn]} / (2x[S]) where [Ag], [In], [Ga], [Zn] and [S] are the molar contents of silver, indium, gallium and sulfur, respectively, in the nanoparticles.
[0141] In one embodiment, the semiconductor nanoparticles may or may not further comprise copper. The charge balance value may be 1.8 or less, 1.75 or less, 1.7 or less, 1.65 or less, 1.6 or less, 1.55 or less, 1.5 or less, 1.45 or less, 1.4 or less, 1.35 or less, 1.33 or less, 1.31 or less, 1.3 or less, 1.29 or less, 1.28 or less, 1.27 or less, 1.26 or less, 1.25 or less, 1.24 or less, 1.23 or less, 1.22 or less, 1.21 or less, 1.2 or less, 1.15 or less, 1.1 or less, or 1.05 or less.
[0142] The charge balance value can be 0.81 or more, 0.85 or more, 0.9 or more, 0.95 or more, 0.97 or more, 0.99 or more, 1 or more, 1.01 or more, 1.02 or more, 1.03 or more, 1.04 or more, 1.05 or more, 1.06 or more, 1.07 or more, 1.08 or more, 1.09 or more, 1.1 or more, 1.11 or more, 1.12 or more, 1.13 or more, 1.14 or more, 1.15 or more, 1.16 or more, 1.17 or more, 1.18 or more, 1.19 or more, 1.2 or more, 1.21 or more, 1.22 or more, 1.23 or more, 1.24 or more, or 1.25 or more.
[0143] In one embodiment, the semiconductor nanoparticles can have a molar ratio of sulfur to the sum of silver, indium, and gallium (S / (Ag+In+Ga)) of 0.65 or more, 0.68 or more, 0.7 or more, 0.75 or more, 0.8 or more, 0.85 or more, 0.9 or more, 0.95 or more, 1 or more, 1.1 or more, 1.2 or more, 1.3 or more, 1.35 or more, 1.36 or more, 1.38 or more, 1.4 or more, 1.45 or more, 1.5 or more, 1.7 or more, or 1.8 or more. The semiconductor nanoparticles can have a molar ratio of sulfur to the sum of silver, indium, and gallium (S / (Ag+In+Ga)) of 3 or less, 2.5 or less, 2 or less, 1.9 or less, 1.88 or less, 1.6 or less, 1.55 or less, 1.5 or less, 1.45 or less, 1.4 or less, 1.35 or less, 1.33 or less, 1.3 or less, 1.25 or less, 1.2 or less, or 1.17 or less, 1.15 or less, 1.09 or less, 1.05 or less, or 1.02 or less.
[0144] In one embodiment, the semiconductor nanoparticles may have a combined molar ratio of indium and gallium to silver ((In+Ga) / Ag) of 1.3 or more, 1.4 or more, 1.5 or more, 1.65 or more, 1.7 or more, 1.75 or more, 1.8 or more, 1.85 or more, 1.9 or more, 1.95 or more, 1.99 or more, 2 or more, 2.1 or more, 2.2 or more, 2.3 or more, or 2.35 or more. The combined molar ratio of indium and gallium to silver ((In+Ga) / Ag) may be 7 or less, 6.5 or less, 6.3 or less, 6 or less, 5.9 or less, 5.7 or less, 5.66 or less, 5.5 or less, 5.3 or less, 5.1 or less, 4.5 or less, 4 or less, 3.5 or less, 3.2 or less, 3 or less, 2.8 or less, 2.6 or less, or 2.4 or less.
[0145] The semiconductor nanoparticles may have a molar ratio of gallium to indium (Ga / In) in the range of 2.5 or more, 2.55 or more, 2.6 or more, 2.65 or more, 2.7 or more, 2.75 or more, 2.8 or more, 2.85 or more, 2.9 or more, 2.95 or more, 3 or more, 3.05 or more, 3.1 or more, 3.15 or more, 3.2 or more, 3.25 or more, 3.3 or more, 3.35 or more, 3.4 or more, 3.45 or more, or 3.5 or more; 10 or less, 9 or less, 8 or less, 7 or less, 6 or less, 5.55 or less, 5.5 or less, 5.3 or less, 5.1 or less, 5 or less, 4.9 or less, 4.7 or less, 4.5 or less, 4.3 or less, 4.2 or less, 4.1 or less, 4 or less, 3.9 or less, 3.8 or less, 3.7 or less, 3.6 or less, or 3.55 or less; or any combination thereof.
[0146] In one embodiment, the semiconductor nanoparticles may have a molar ratio of gallium to the sum of indium and gallium of 0.5 or more, 0.55 or more, 0.6 or more, 0.65 or more, 0.7 or more, 0.75 or more, 0.8 or more, or 0.85 or more. The molar ratio of gallium to the sum of indium and gallium may be 0.99 or less, 0.98 or less, 0.97 or less, 0.96 or less, 0.95 or less, 0.94 or less, 0.93 or less, 0.92 or less, 0.91 or less, 0.9 or less, or 0.83 or less.
[0147] In one embodiment, the semiconductor nanoparticles may have a molar ratio of gallium to sulfur (Ga / S) of 0.1 or more, 0.15 or more, 0.2 or more, 0.25 or more, 0.3 or more, 0.31 or more, 0.32 or more, 0.33 or more, 0.34 or more, 0.35 or more, 0.38 or more, 0.4 or more, 0.47 or more, 0.5 or more, 0.53 or more, 0.55 or more, 0.56 or more, 0.58 or more, 0.6 or more, 0.62 or more. The molar ratio of gallium to sulfur (Ga / S) may be 1 or less, 0.9 or less, 0.8 or less, 0.6 or less, 0.55 or less, 0.45 or less, 0.42 or less, 0.41 or less, or 0.4 or less.
[0148] In one embodiment, the semiconductor nanoparticles may have a molar ratio of silver to sulfur (Ag / S) of 0.03 or more, 0.05 or more, 0.06 or more, 0.07 or more, 0.08 or more, 0.09 or more, 0.1 or more, 0.15 or more, 0.2 or more, 0.25 or more, 0.3 or more, 0.35 or more, 0.4 or more, or 0.45 or more. The molar ratio of silver to sulfur (Ag / S) may be 1 or less, 0.6 or less, 0.5 or less, 0.4 or less, 0.38 or less, 0.36 or less, 0.35 or less, 0.3 or less, 0.25 or less, 0.24 or less, or 0.23 or less.
[0149] In some embodiments, the semiconductor nanoparticles may have a molar ratio of indium to sulfur (In / S) of 0.01 or more, 0.05 or more, 0.08 or more, or 0.09 or more, 0.1 or more. The molar ratio of indium to sulfur (In / S) may be 0.5 or less, 0.4 or less, 0.3 or less, 0.25 or less, 0.15 or less, 0.14 or less, 0.13 or less, or 0.12 or less.
[0150] In one embodiment, the semiconductor nanoparticles may have a molar ratio of silver to indium (Ag / In) in the range of 0.1-5, 1.5-3.5, 1.7-3, 1.8-2.94, 1.88-2, or any combination thereof.
[0151] In one embodiment, the molar ratio of zinc to indium in the semiconductor nanoparticles can be 0.1 or more, 0.3 or more, 0.4 or more, 0.5 or more, 0.7 or more, 0.75 or more, 0.78 or more, 0.9 or more, 1 or more, 1.2 or more, 1.4 or more, 1.6 or more, 1.7 or more, 1.72 or more, 2 or more, 2.5 or more, 3 or more, 3.5 or more, 4 or more, or 4.5 or more. In one embodiment, the molar ratio of zinc to indium in the semiconductor nanoparticles can be 20 or less, 15 or less, 10 or less, 8 or less, 6 or less, 4 or less, 3 or less, 2.5 or less, 2 or less, 1.9 or less, 1.85 or less, 1.7 or less, 1.75 or less, or 1.72 or less.
[0152] The content of the semiconductor nanoparticles in the ink composition (or the semiconductor nanoparticle-polymer composite) can be appropriately adjusted taking into consideration the desired end use (e.g., color filters, etc.). In one embodiment, the content of the semiconductor nanoparticles in the ink composition (or the semiconductor nanoparticle-polymer composite) can be 1 wt% or more, for example, 2 wt% or more, 3 wt% or more, 4 wt% or more, 5 wt% or more, 6 wt% or more, 7 wt% or more, 8 wt% or more, 9 wt% or more, 10 wt% or more, 12 wt% or more, 14 wt% or more, 15 wt% or more, 17 wt% or more, 19 wt% or more, 20 wt% or more, 23 wt% or more, 25 wt% or more, 27 wt% or more, 30 wt% or more, 33 wt% or more, 35 wt% or more, 37 wt% or more, or 40 wt% or more, based on the total solid content or total weight of the composition or composite (hereinafter, the total solid content or total weight may be the total solid content or total weight of the composition, or the total solid content or total weight of the composite). In the ink composition (or semiconductor nanoparticle-polymer composite), the content of the semiconductor nanoparticles may be 70% by weight or less, for example, 65% by weight or less, 60% by weight or less, 55% by weight or less, 50% by weight or less, or 45% by weight or less, based on the total solid content or total weight. The weight percentage of a component relative to the total solid content in the composition may represent the content of the component in the composite described below. The total solid content is the total weight of the solid content. In one embodiment, the total weight of the composition or composite may be the total solid content (i.e., the total weight of the solids).
[0153] The ligand-exchanged semiconductor nanoparticles may exhibit different dispersibility than before the ligand exchange. In one embodiment, the semiconductor nanoparticles are well dispersed in a liquid vehicle (e.g., a monomer described herein) for an ink composition. In one embodiment, the semiconductor nanoparticles in the ink composition may be dispersed in a polymerizable monomer and exhibit a colloidal dispersion.
[0154] In one embodiment of the ink composition, the polymerizable monomer comprises a compound containing one or more (e.g., 2 or more, 3 or more, and 10 or less) carbon-carbon double bonds. The monomer may be a precursor for an insulating polymer. The monomer is polymerized by light or heat.
[0155] In the ink composition, the monomer has the formula: [ka] In the above Chemical Formula 3, X is an organic group having 2 to 30 carbon atoms and a carbon-carbon double bond, L 2 is a single bond, a carbon atom, a substituted or unsubstituted alkylene group having 1 to 50 carbon atoms, a substituted or unsubstituted cycloalkylene group having 3 to 50 carbon atoms (e.g., 6 to 30 carbon atoms), a substituted or unsubstituted cycloalkenylene group having 3 to 50 carbon atoms (e.g., 6 to 30 carbon atoms), a substituted or unsubstituted arylene group having 6 to 50 carbon atoms, a substituted or unsubstituted heteroarylene group having 3 to 30 carbon atoms, a group having one or more oxyalkylene units [(RO)n, where R is a substituted or unsubstituted alkylene such as ethylene, isopropylene, butylene, and n is 1 or more and 500 or less], sulfonyl (-S(=O) 2-), carbonyl (-C(=O)-), ether (-O-), sulfide (-S-), sulfoxide (-S(=O)-), ester (-C(=O)O-), amide (-C(=O)NR-) (wherein R is hydrogen or a straight or branched chain alkyl group having 1 to 10 carbon atoms), imine (-NR-) (wherein R is hydrogen or a straight or branched chain alkyl group having 1 to 10 carbon atoms), or a combination thereof; Y is a single bond, a substituted or unsubstituted alkylene group having 1 to 30 carbon atoms, a substituted or unsubstituted alkenylene group having 2 to 30 carbon atoms, or a sulfonyl (-S(=O) 2 -), carbonyl (-C(=O)-), ether (-O-), sulfide (-S-), sulfoxide (-S(=O)-), ester (-C(=O)O-), amide (-C(=O)NR-) (wherein R is hydrogen or a straight or branched chain alkyl group having 1 to 10 carbon atoms), imine (-NR-) (wherein R is hydrogen or a straight or branched chain alkyl group having 1 to 10 carbon atoms), or a combination thereof; n is an integer equal to or greater than 1, k is an integer equal to or greater than 1, The sum of n and k is an integer of 2 or greater (eg, 3 or greater, or 4 or greater and 10 or less, or 5 or less). n is determined by the valence of Y. k is determined by the valence of L. X can include a vinyl group, a (meth)acrylate group, or a combination thereof.
[0156] The monomers include polyethylene glycol methacrylate, polypropylene glycol methacrylate, polyethylene glycol dimethacrylate, polypropylene glycol dimethacrylate, substituted or unsubstituted alkyl (meth)acrylate, ethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, 1,4-butanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, neopentyl glycol di(meth)acrylate, pentaerythritol di(meth)acrylate, pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, and the like. The acrylate or acrylate combination may include glyceryl ether, glyceryl ether, acrylate, dipentaerythritol di(meth)acrylate, dipentaerythritol tri(meth)acrylate, dipentaerythritol penta(meth)acrylate, dipentaerythritol hexa(meth)acrylate, bisphenol A epoxy acrylate, bisphenol A di(meth)acrylate, trimethylolpropane tri(meth)acrylate, novolac epoxy (meth)acrylate, ethyl glycol monomethyl ether (meth)acrylate, tris(meth)acryloyloxyethyl phosphate, propylene glycol di(meth)acrylate, diacryloyloxyalkane, or combinations thereof.
[0157] The monomers can include substituted or unsubstituted di(meth)acrylate compounds, substituted or unsubstituted tri(meth)acrylate compounds, substituted or unsubstituted tetra(meth)acrylate compounds, substituted or unsubstituted penta(meth)acrylate compounds, substituted or unsubstituted hexa(meth)acrylate compounds, or combinations thereof.
[0158] The content of the monomer may be 0.5% by weight or more, for example, 1% by weight or more, 2% by weight or more, 3% by weight or more, 5% by weight or more, 10% by weight or more, 20% by weight or more, 30% by weight or more, or 40% by weight or more, based on the total weight or total solid content of the composition. The content of the photopolymerizable monomer may be 99% or less, 90% or less, 80% or less, 70% or less, 60% or less, 50% or less, 45% or less, 28% or less, 25% or less, 23% or less, 20% or less, 18% or less, 17% or less, 16% or less, or 15% or less by weight, based on the total weight or total solid content of the composition.
[0159] The ink composition can further include an initiator, metal oxide particles, or a combination thereof. The (photo)initiator contained in the composition is for (photo)polymerization of the above-mentioned monomer. The initiator is a compound that can generate radical species under mild conditions (e.g., by heat or light) to promote a radical reaction (e.g., radical polymerization of a monomer). The initiator may be a thermal initiator or a photoinitiator. The initiator is not particularly limited and can be appropriately selected.
[0160] The thermal initiator may include, but is not limited to, azobisisobutyronitrile, benzoyl peroxide, etc. The photoinitiator may include, but is not limited to, a triazine-based compound, an acetophenone compound, a benzophenone compound, a thioxanthone compound, a benzoin compound, an oxime ester compound, an aminoketone compound, a phosphine or phosphine oxide compound, a carbazole-based compound, a diketone compound, a sulfonium borate-based compound, a diazo-based compound, a non-imidazole-based compound, or a combination thereof. The initiator can include Irgacure 754, hydroxycyclohexyl phenyl ketone (Irgacure 184, CAS 947-19-3), 2,4,6-trimethylbenzoyl diphenylphosphine oxide (Irgacure TPO, CAS 75980-60-8), oxyphenyl-acetic acid 2[2-oxo-2-phenyl-acetoxy-ethoxy]-ethyl ester, or combinations thereof.
[0161] In the ink composition, the content of the initiator may be appropriately adjusted in consideration of the type and content of the polymerizable monomer used. In one embodiment, the content of the initiator may be, but is not limited to, 0.01 wt % or more, for example, 1 wt % or more, and 10 wt % or less, for example, 9 wt % or less, 8 wt % or less, 7 wt % or less, 6 wt % or less, or 5 wt % or less, based on the total weight (or total solid content) of the composition.
[0162] In the composition or composite, the metal oxide fine particles are TiO 2 , SiO 2 , BaTiO 3 , B.A. 2 TiO 4, ZnO, or combinations thereof. The content of the metal oxide in the composition (or composite) can be 1 wt% or more, 2 wt% or more, 3 wt% or more, 5 wt% or more, or 10 wt% or more and 50 wt% or less, 40 wt% or less, 30 wt% or less, 25 wt% or less, 20 wt% or less, 15 wt% or less, 10 wt% or less, 7 wt% or less, 5 wt% or less, or 3 wt% or less based on the total weight or total solids content of the composition or composite. The diameter of the metal oxide particles is not particularly limited and can be appropriately selected. The diameter of the metal oxide particles can be 100 nm or more, for example, 150 nm or more or 200 nm or more and 1000 nm or less, or 800 nm or less.
[0163] The ink composition according to an embodiment may be prepared by admixing the above-mentioned components. The mixing method is not particularly limited and may be appropriately selected. The ink composition according to an embodiment may further include a volatile organic solvent, or may not include a volatile organic solvent. The ink composition according to an embodiment may form a colloidal dispersion liquid without using a volatile organic solvent. The volatile organic solvent may have a boiling point in the range of 179° C. or more and 324° C. or less, 200° C. to 300° C., or a combination thereof. The volatile organic solvent may be alkylnaphthalene, alkoxynaphthalene, alkylbenzene, aryl, alkyl-substituted benzene, cycloalkylbenzene, C 9 -C 20It may contain alkane, diarylether, alkyl benzoate, aryl benzoate, alkoxy-substituted benzene or a combination thereof. The volatile organic solvent may include 1-tetralone, 3-phenoxytoluene, acetophenone, 1-methoxynaphthalene, n-octylbenzene, n-nonylbenzene, 4-methylanisole, n-decylbenzene, p-diisopropylbenzene, pentylbenzene, tetralin, cyclohexylbenzene, chloronaphthalene, 1,4-dimethylnaphthalene, 3-isopropylbiphenyl, p-methylcumene, dipentylbenzene, o-diethylbenzene, m-diethylbenzene, p-diethylbenzene, 1,2,3,4-tetramethylbenzene, 1,2,3,5-tetramethylbenzene, 1,2,4,5-tetrametylbenzene, butylbenzene, dodecylbenzene, 1-methylnaphthalene, 1,2,4-trichlorobenzene, diphenyl ether, diphenylmethane, 4-isopropylbiphenyl, benzyl benzoate, 1,2-bi(3,4-dimethylphenyl)ethane, 2-isopropylnaphthalene, dibenzyl ether, or combinations thereof. In one embodiment, the organic solvent used in the ink composition may include 1-methylnaphthalene, n-octylbenzene, 1-methoxynapththalene, 3-phenoxytoluene, cyclohexylbenzene, 4-methylanisole, n-decylbenzene, or combinations thereof.
[0164] In one embodiment, the ink composition can provide a nanoparticle-composite or a pattern thereof by polymerization (e.g., photopolymerization). The ink composition can provide a semiconductor nanoparticle-polymer composite by polymerization, the semiconductor nanoparticle-polymer composite including a matrix containing a polymerization product of the monomer and semiconductor nanoparticles disposed or dispersed within the matrix. The semiconductor nanoparticle-polymer composite can be heat-treated at 100° C. or higher or 180° C. for 30 minutes, and the retention rate obtained by the following formula can be 95% or higher, 96% or higher, 97% or higher, 98% or higher, 99% or higher, or 100% or higher: Retention rate (%)=[EQE2 / EQE1]×100 In the above formula, EQE1 is the external quantum efficiency of the semiconductor nanoparticle-polymer composite before heat treatment after polymerization, and EQE2 is the external quantum efficiency of the semiconductor nanoparticle-polymer composite after heat treatment.
[0165] The retention rate may be greater than 100%, for example, 101% or more, 102% or more, 103% or more, or 104% or more.
[0166] In one embodiment, the composition can be polymerized to provide a semiconductor nanoparticle-polymer composite or pattern thereof. In one embodiment, the semiconductor nanoparticle-polymer composite includes a matrix and semiconductor nanoparticles disposed (e.g., dispersed) within the matrix. The semiconductor nanoparticles include a Group 11-13-16 compound including silver, indium, gallium, and sulfur. The semiconductor nanoparticles or the semiconductor nanoparticle-polymer composite can further include fluorine. The semiconductor nanoparticles or the semiconductor nanoparticle-polymer composite can further include a halogen, e.g., chlorine. The semiconductor nanoparticle-polymer composite or the semiconductor nanoparticle can further include a first organic ligand.
[0167] In the composite, the content of the semiconductor nanoparticles may be 1 wt% or more, 1.5 wt% or more, 2 wt% or more, 5 wt% or more, 6 wt% or more, 7 wt% or more, 8 wt% or more, 9 wt% or more, 10 wt% or more, 12 wt% or more, 14 wt% or more, 15 wt% or more, 17 wt% or more, 19 wt% or more, 20 wt% or more, 23 wt% or more, 25 wt% or more, 27 wt% or more, 30 wt% or more, 33 wt% or more, 35 wt% or more, 37 wt% or more, 40 wt% or more, 45 wt% or more, and 99% or less, 90% or less, 80% or less, 70% or less, 65% or less, 60% or less, 55% or less, or 50% or less by weight, based on the total weight of the composite.
[0168] The content of the semiconductor nanoparticles may be referred to in the description of the ink composition. The composite of one embodiment may further include metal oxide fine particles, and the type and content thereof may be referred to in the description of the ink composition.
[0169] The content of the matrix in the semiconductor nanoparticle-polymer composite may be 1 wt% or more, 5 wt% or more, 10 wt% or more, 15 wt% or more, 20 wt% or more, 25 wt% or more, 30 wt% or more, 35 wt% or more, 40 wt% or more, 45 wt% or more, 50 wt% or more, 55 wt% or more, 60 wt% or more, 65 wt% or more, or 70 wt% or more based on the total weight of the composite. The content of the matrix in the semiconductor nanoparticle-polymer composite may be 99 wt% or less, 98 wt% or less, 95 wt% or less, 93 wt% or less, 90 wt% or less, 80 wt% or less, 70 wt% or less, 60 wt% or less, 50 wt% or less, 40 wt% or less, or 30 wt% or less.
[0170] The matrix can be a polymerization product of a polymerizable monomer (eg, an electrically insulating polymer), with details regarding the semiconductor nanoparticles, polymerizable monomers, and first organic ligands being as described herein.
[0171] The semiconductor nanoparticle-polymer composite or the ink composition can have a molar ratio of fluorine to indium (F / In) of greater than 0, greater than 0.2, 0.21 or more, 0.23 or more, 0.25 or more, 0.27 or more, 0.29 or more, 0.3 or more, 0.35 or more, 0.37 or more, 0.4 or more, 0.5 or more, 0.8 or more, 1 or more, 1.3 or more, 1.4 or more, 1.5 or more, 1.8 or more, 2 or more, 2.2 or more, 2.5 or more, 2.8 or more, 3 or more, 3.4 or more, or 3.5 or more. The molar ratio of fluorine to indium (F / In) in the semiconductor nanoparticle-polymer composite or the ink composition can be 10 or less, 8 or less, 6 or less, 5 or less, 4.5 or less, 4 or less, 3.8 or less, 3.6 or less, 3.5 or less, 3 or less, 2.8 or less, 2.6 or less, 2.3 or less, 2 or less, 1.5 or less, 1 or less, 0.8 or less, 0.6 or less, 0.5 or less, or 0.45 or less.
[0172] In the semiconductor nanoparticle-polymer composite or the ink composition, the molar ratio of fluorine to silver (F / Ag) may be greater than 0, 0.25 or more, 0.3 or more, 0.33 or more, 0.35 or more, 0.37 or more, 0.39 or more, 0.4 or more, 0.41 or more, 0.43 or more, 0.5 or more, 0.7 or more, 0.8 or more, 0.9 or more, 0.95 or more, 0.99 or more, 1 or more, or 1.2 or more. In the semiconductor nanoparticle-polymer composite or the ink composition, the molar ratio of fluorine to silver (F / Ag) may be 10 or less, 5 or less, 4 or less, 3 or less, 2.5 or less, 2 or less, 1.5 or less, 1 or less, 0.8 or less, 0.6 or less, 0.5 or less, or 0.45 or less.
[0173] In the semiconductor nanoparticle-polymer composite or the ink composition, the molar ratio of fluorine to sulfur (F / S) may be greater than 0, 0.05 or more, 0.09 or more, 0.1 or more, 0.11 or more, 0.12 or more, 0.13 or more, 0.2 or more, 0.25 or more, 0.3 or more, 0.35 or more, 0.4 or more, 0.45 or more, 0.5 or more, or 0.55 or more. In the semiconductor nanoparticle-polymer composite or the ink composition, the molar ratio of fluorine to sulfur (F / S) may be 10 or less, 5 or less, 2 or less, 1.5 or less, 1.3 or less, 1 or less, 0.9 or less, 0.8 or less, 0.7 or less, 0.65 or less, 0.6 or less, 0.57 or less, 0.55 or less, 0.5 or less, 0.49 or less, 0.42 or less, 0.4 or less, 0.3 or less, or 0.2 or less.
[0174] The fluorine content (or molar ratio) can be confirmed by an appropriate analytical means (eg, XPS, TEM-EDX, etc.). In one embodiment, the semiconductor nanoparticle-polymer composite may exhibit a peak assigned to fluorine in XPS analysis, the maximum intensity of which may be in the range of 680 eV to 694 eV, e.g., 684 eV to 690 eV, 686 eV to 689 eV, or any combination thereof.
[0175] The semiconductor nanoparticle-polymer composite of one embodiment may exhibit improved optical properties. The nanoparticles or composites including the nanoparticles of one embodiment may have improved optical properties (e.g., increased luminous efficiency and narrower half-width) along with an increased level of blue light absorptivity (e.g., improved excitation light absorptivity), and may emit light of a desired wavelength (e.g., first light). For example, when the composite is placed in an integrating hemisphere and irradiated with incident light having a wavelength of 450 nm to measure the amount of first light emitted from the composite, the semiconductor nanoparticle-polymer composite may have an external quantum efficiency (EQE) of 27% or more, or 30% or more, as calculated by the following formula: External quantum efficiency (%) = [A / B] x 100 A: Light intensity of the first light B: Amount of incident light
[0176] The external quantum efficiency may be 31% or more, 32% or more, 33% or more, 34% or more, 35% or more, 36% or more, 37% or more, 38% or more, 39% or more, or 40% or more. The external quantum efficiency may be 30% or more to 50%, or 32% to 45%. The amount of light can be easily and reproducibly measured using appropriate tools (e.g., a detector such as an integrating (hemi)sphere and a photodetector).
[0177] The semiconductor nanoparticle-polymer composite can have an incident light absorptance of 70% or more, 80% or more, 85% or more, 88% or more, 89% or more, 90% or more, 91% or more, 92% or more, 93% or more, or 94% or more, given by the following formula: Incident light absorption rate (%) = [(B-B') / B] x 100 B: Amount of incident light B': Amount of incident light that passed through the complex
[0178] The composite can have an incident light absorptance of 70% or more, 73% or more, 75% or more, 77% or more, 80% or more, 83% or more, 85% or more, 87% or more, 90% or more, 93% or more, 95% or more, 97% or more, or 99% or more. The composite can have an incident light absorptance of 70%-100%, 80%-98%, 95%-99%, 96%-98%, 90-94%, or a combination thereof.
[0179] The semiconductor nanoparticle-polymer composite may have an internal quantum efficiency (IEQ) of 29% or greater, or 35% or greater, given by the formula: Internal quantum efficiency (%) = [A / (B-B')] x 100 A: Light intensity of the first light B: Amount of incident light B': Amount of incident light that passed through the complex
[0180] The internal quantum efficiency may be 31% or more, 32% or more, 33% or more, 34% or more, 35% or more, 36% or more, 37% or more, 38% or more, 39% or more, or 40% or more. The external quantum efficiency may be 30% or more to 60%, or 32% to 50%.
[0181] The composite may have the form of a sheet.The composite may be in the form of a patterned film.
[0182] The (polymer) matrix may comprise the polymerization product of the monomers described above. The matrix may comprise a linear polymer, a cross-linked polymer, or a combination thereof. The cross-linked polymer may comprise a thiolene resin, a cross-linked poly(meth)acrylate, a cross-linked polyurethane, a cross-linked epoxy resin, a cross-linked vinyl polymer, a cross-linked silicone resin, or a combination thereof. In one embodiment, the cross-linked polymer may be the polymerization product of the polymerizable monomers described above and optionally a multi-thiol compound.
[0183] The linear polymer can include repeat units derived from a carbon-carbon unsaturated bond (e.g., a carbon-carbon double bond). The repeat units can include a carboxylic acid group. The linear polymer can include ethylene repeat units. The carboxylic acid group-containing repeat units can include units derived from a monomer containing a carboxylic acid group and a carbon-carbon double bond, units derived from a monomer having a dianhydride residue, or a combination thereof.
[0184] The composite may have a predetermined thickness and may contain a predetermined content of the nanoparticles. The ink composition or a composite produced therefrom may have the form of a film having a thickness of 10 micrometers. The composite may have the form of a film or pattern, and the thickness of the composite may be, for example, 30 μm or less, for example, 25 um or less, 20 um or less, 15 um or less, 10 um or less, 8 um or less, or 7 um or less, and may be more than 2 um, for example, 3 um or more, 3.5 um or more, 4 um or more, 5 um or more, 6 um or more, 7 um or more, 8 um or more, 9 um or more, or 10 um or more.
[0185] The composite can be used in a sheet containing luminescent particles disposed over a light source, or in a color conversion panel (eg, a luminescent color filter).
[0186] Thus, one embodiment relates to a color conversion layer (e.g., color conversion structure) including the semiconductor nanoparticles or the semiconductor nanoparticle-polymer composite, or a color conversion panel including the same. The color conversion layer (e.g., color conversion structure) may include the composite of one embodiment or a patterned film thereof. The color conversion layer may include a color conversion area. The color conversion area can include a first area configured to emit light of a predetermined wavelength (e.g., green light) (e.g., upon illumination with an excitation light). In one embodiment, the first area can correspond to a green pixel.
[0187] The color conversion area may further include (e.g., one or more) second areas configured to emit light (e.g., red light) at a wavelength different from the light emitted from the first area (e.g., upon irradiation with excitation light). The second area may correspond to a red pixel. The first area and the second area may each include a semiconductor nanoparticle-polymer composite. The emission peak wavelengths of the green light and the red light are as defined herein. The color conversion panel may further include (one or more) third areas that emit or pass a third light (e.g., blue light). The third light may include excitation light (blue light and optionally green light). The third light may include blue light having a maximum peak wavelength in the range of 380 nm or more (e.g., 440 nm or more, 445 nm or more, 450 nm or more, or 455 nm or more) and 480 nm or less (475 nm or less, 470 nm or less, 465 nm or less, or 460 nm or less). Semiconductor nanoparticle-polymer composites according to one embodiment are disposed in the first region and / or the second region.
[0188] FIG. 1a is a schematic cross-sectional view of a color conversion panel according to an embodiment. Referring to FIG. 1a, the color conversion panel may further include a partition (e.g., a black matrix (BM), a bank, or a combination thereof) that defines each region of the color conversion layer. FIG. 1b relates to an electronic device (display device) including a color conversion layer (e.g., a color conversion structure) and a light source according to another embodiment. In the electronic device, the color conversion layer is disposed on an LED on chip (e.g., a micro LED on chip). Referring to FIG. 1b, a circuit (Si Driver IC) for driving a light source (e.g., a blue LED) configured to emit incident light (e.g., blue light) is disposed under the light source. The color conversion layer may include a first composite including nanoparticles that emit a first light (e.g., green light), a second composite including nanoparticles that emit a second light (e.g., red light), or a third composite that emits or passes a third light (e.g., incident light or blue light). A partition (e.g., an inorganic material-based or organic material-based such as silicon or silicon oxide) is disposed between each composite. The partition may include a trench hole, a via hole, or a combination thereof. A first optical element (e.g., an absorptive color filter) is disposed on the light extraction surface of the color conversion layer. An additional optical element, such as a microlens, is further disposed on the first optical element.
[0189] A color conversion layer or a patterned film of a nanoparticle composite can be manufactured by an inkjet printing method using the ink composition of one embodiment. Referring to FIG. 2, such a method can include the steps of: preparing an ink composition; providing a substrate (e.g., on which pixel regions are patterned with electrodes and, optionally, banks or trench-type partitions); and depositing the ink composition on the substrate (or the pixel regions) to form, for example, a first composite layer (or a first region). The method can include depositing the ink composition on the substrate (or the pixel regions) to form, for example, a second composite layer (or a second region). The formation of the first composite layer and the formation of the second composite layer can be performed simultaneously or sequentially.
[0190] The deposition of the ink composition can be carried out using a suitable liquid crystal ejection device such as an ink jet or nozzle printing system (e.g., having an ink reservoir and one or more printheads). The deposited ink composition can be heated to remove the solvent and polymerized to provide the (first or second) composite layer. The polymerization can include thermal polymerization, photopolymerization, or a combination thereof. In the case of photopolymerization, the ink composition can be irradiated with light of a predetermined wavelength (e.g., 200 nm or more and 450 nm or less). Such a method can form a highly precise nanoparticle-polymer composite film or patterned membrane in a simple manner in a short time.
[0191] The above-mentioned nanoparticles, a composite (pattern) containing the nanoparticles, or a color conversion panel containing the nanoparticles are included in electronic devices. Such electronic devices may include, but are not limited to, a display device, a light-emitting diode (LED), an organic light-emitting diode (OLED), a quantum dot LED, a sensor, a solar cell, an imaging sensor, a photodetector, or a liquid crystal display device. The above-mentioned semiconductor nanoparticles or a composite containing the nanoparticles are included in electronic apparatus. Such electronic devices may include, but are not limited to, a mobile terminal device, a monitor, a notebook PC, a television, a light-emitting board, a camera, an automobile, and the like. The electronic device may be a mobile terminal device, a monitor, a notebook PC, or a television including a display device (or a light-emitting element) including a quantum dot. The electronic device may be a camera or a mobile terminal device including an image sensor including a quantum dot. The electronic device may be a camera or an automobile including a photodetector including a quantum dot.
[0192] In one embodiment, an electronic device or display device (e.g., a display panel) may further include a color conversion layer (or color conversion panel) and optionally a light source. The light source is configured to provide incident light to the color conversion layer or the color conversion panel. In one embodiment, a display panel includes a light emitting panel (or light source), the above-mentioned color conversion panel, and a light-transmitting layer located between the light emitting panel and the color conversion panel. The color conversion panel includes a substrate, and the color conversion layer is disposed on the substrate. (See: Figures 3a and 4)
[0193] The light source or light emitting panel (if present) is configured to provide incident light to the light emitting elements, the incident light can have a light emission peak wavelength in the range of 440 nm or more, e.g., 450 nm or more and 580 nm or less, 550 nm or less, 540 nm or less, 530 nm or less, 520 nm or less, 510 nm or less, 500 nm or less, 490 nm or less, 480 nm or less, 470 nm or less, or 460 nm or less.
[0194] In one embodiment, an electronic device (e.g., a light-emitting type device) may include a sheet of the nanoparticle composite. Referring to FIG. 3b, the device includes a backlight unit 410 and a liquid crystal panel 420, and the backlight unit 410 may include a quantum dot polymer composite sheet (QD sheet). Specifically, the backlight unit 410 may have a structure in which a reflector, a light guide plate (LGP), a light source (e.g., blue LED), a quantum dot polymer composite sheet (QD sheet), and an optical film (e.g., a prism, a double brightness enhance film (DBEF)) are stacked. The liquid crystal panel 420 may be disposed on the backlight unit 410 and may have a structure including liquid crystal and a color filter between two polarizers (Pol). The quantum dot polymer composite sheet (QD sheet) may include quantum dots that absorb light from a light source and emit red light and quantum dots that emit green light. Blue light provided from the light source is converted into white light by combining with the red light and green light emitted from the quantum dots through the quantum dot polymer composite sheet. This white light is separated into blue, green, and red light by the color filter in the LCD panel and emitted to the outside for each pixel. Referring to Figure 4b, the backlight unit (BLU) may be a direct type BLU without a light guide plate, or may include multiple LEDs (e.g., mini LEDs).
[0195] The color conversion panel may include a substrate, and the color conversion layer may be disposed on the substrate. The color conversion layer or the color conversion panel may include a patterned film of nanoparticle composites. The patterned film may include repeating sections configured to emit desired light. The second region may be a red light emitting section. The first region may be a green light emitting section. The third region may be a section that emits or transmits blue light. Details regarding the first, second, and third regions are as described above.
[0196] The light emitting panel or the light source may be an element that emits excitation light. The excitation light may include blue light and optionally green light. The light source may include an LED. The light source may include an organic LED (OLED). The light source may include a micro LED. An optical element that blocks (e.g., reflects or absorbs) blue light (and optionally green light), such as a blue light (and optionally green light) blocking layer or a first optical filter described below, is disposed on the front surface (light emitting surface) of the first region and the second region. When the light source includes a blue light emitting organic light emitting diode and a green light emitting organic light emitting diode, a green light removing filter is further disposed on the third section through which the blue light passes.
[0197] The light-emitting panel or the light source includes a plurality of light-emitting units corresponding to the first and second regions, respectively, and the light-emitting units may include a first electrode and a second electrode facing each other, and an (organic) electroluminescent layer disposed between the first electrode and the second electrode. The electroluminescent layer may include an organic light-emitting material. For example, each light-emitting unit of the light source may include an electroluminescent element (e.g., an organic light-emitting diode) configured to emit light of a predetermined wavelength (e.g., blue light, green light, or a combination thereof). The structures and materials of the electroluminescent element and the organic light-emitting diode are known and are not particularly limited.
[0198] The display panel and the color conversion panel will be described in more detail below with reference to the drawings. 3a and 4a, a display panel or electronic device 1000 according to an embodiment includes a light emitting panel 100 or a light source, and a color conversion panel 200. The display panel or electronic device may further include, but is not limited to, a light transmitting layer 300 located between the light emitting panel 100 and the color conversion panel 200, a bonding material 400 bonding the light emitting panel 100 and the color conversion panel 200, or a combination thereof. The light transmitting layer may include a passivation layer, a filling material, an encapsulation layer, or a combination thereof. The light transmitting layer material may be appropriately selected and is not particularly limited. The light transmitting layer material may include an inorganic material, an organic material, an organic-inorganic hybrid material, or a combination thereof.
[0199] The light-emitting panel 100 and the color conversion panel 200 face each other with a light-transmitting layer 300 therebetween, and the color conversion panel 200 is disposed in a direction in which light is emitted from the light-emitting panel 100. The bonding material 400 is disposed along the periphery of the light-emitting panel 100 and the color conversion panel 200, and may be, for example, a sealing material.
[0200] Referring to FIG. 5a, a display panel 1000 according to an embodiment includes a display area 1000D for displaying an image, and a non-display area 1000P located around the display area 1000D and having a binder 400 disposed thereon. The display area 1000D includes a plurality of pixels PX arranged along rows (e.g., in the x direction) and / or columns (e.g., in the y direction), and each pixel PX includes a plurality of sub-pixels PX that display different colors. 1 , P.X. 2 , P.X. 3 Here, as an example, three sub-pixels PX 1 , P.X. 2 , P.X. 3Although the configuration in which each pixel is a single pixel has been shown, the present invention is not limited thereto, and an additional sub-pixel such as a white sub-pixel may be further included, and one or more sub-pixels displaying the same color may be further included. The pixels PX may be arranged, for example, in a Bayer matrix, a PenTile matrix, and / or a diamond matrix, but are not limited thereto.
[0201] Each sub-pixel PX 1 , P.X. 2 , P.X. 3 The first sub-pixel PX can display three primary colors or a combination of three primary colors, for example, red, green, and blue, or a combination thereof. 1 can display red, and the second sub-pixel PX 2 can display green, and the third sub-pixel PX 3 can display the color blue.
[0202] Although the drawings show an example in which all the sub-pixels have the same size, the present invention is not limited thereto, and at least one of the sub-pixels may be larger or smaller than the other sub-pixels. Although the drawings show an example in which all the sub-pixels have the same shape, the present invention is not limited thereto, and at least one of the sub-pixels may have a different shape from the other sub-pixels.
[0203] In one embodiment, a display panel or electronic device, such as a light-emitting panel, may include a substrate and a (e.g., oxide-based) TFT disposed on the substrate, with a light-emitting element disposed on the TFT (e.g., having a tandem structure).
[0204] The light-emitting element may include an emitting layer (e.g., a blue emitting layer, a green emitting layer, or a combination thereof) between opposing first and second electrodes. A charge generating layer is disposed between each of the emitting layers. The first and second electrodes may each be patterned with a plurality of electrode elements to correspond to pixels. The first electrode may be an anode or a cathode. The second electrode may be a cathode or an anode.
[0205] The light emitting device may include an organic LED, a nanorod LED, a mini LED, a micro LED, or a combination thereof. In one embodiment, the mini LED may have a size of, but is not limited to, 100 micrometers (um) or more, 150 um or more, 200 um or more to 1 mm or less, 0.5 mm or less, 0.15 mm or less, or 0.12 mm or less. In one embodiment, the micro LED may have a size of less than 100 micrometers, 50 micrometers or less, or 10 micrometers or less. The size of the micro LED may be, but is not limited to, 0.1 um or more, 0.5 um or more, 1 um or more, or 5 um or more.
[0206] 5b to 5e are cross-sectional views showing examples of light-emitting devices. Referring to FIG. 5b, in one embodiment, the light emitting element 180 may include a first electrode 181 and a second electrode 182 facing each other; an emission layer 183 located between the first electrode 181 and the second electrode 182; and, optionally, auxiliary layers 184 and 185 located between the first electrode 181 and the emission layer 183 and between the second electrode 182 and the emission layer 183.
[0207] The first electrode 181 and the second electrode 182 are disposed to face each other along a thickness direction (e.g., z direction), and one of the first electrode 181 and the second electrode 182 may be an anode and the other may be a cathode. The first electrode 181 may be a transparent electrode, a semi-transparent electrode, or a reflective electrode, and the second electrode 182 may be a transparent electrode or a semi-transparent electrode. The transparent electrode or the semi-transparent electrode may be made of a conductive oxide such as indium tin oxide (ITO), indium zinc oxide (IZO), zinc oxide (ZnO), tin oxide (SnO), aluminum tin oxide (AlTO), and fluorine-doped tin oxide (FTO), or a thin single-layer or multi-layer metal thin film including silver (Ag), copper (Cu), aluminum (Al), magnesium (Mg), magnesium-silver (Mg-Ag), magnesium-aluminum (Mg-Al), or a combination thereof. The reflective electrode may include a metal, a metal nitride, or a combination thereof, such as, but not limited to, silver (Ag), copper (Cu), aluminum (Al), gold (Au), titanium (Ti), chromium (Cr), nickel (Ni), alloys thereof, nitrides thereof (e.g., TiN), or combinations thereof.
[0208] Light emitting layer 183 can emit a first phosphor that emits light having a blue emission spectrum, a second phosphor that emits light having a green emission spectrum, or a combination thereof.
[0209] The maximum emission wavelength of the blue emission spectrum can belong to a wavelength range of about 400 nm or more and less than 500 nm, and within the above range, can belong to a wavelength range of about 410 nm to 490 nm, about 420 nm to 480 nm, 430 nm to 470 nm, 440 nm to 465 nm, 445 nm to 460 nm, 450 nm to 458 nm, or a combination thereof.
[0210] The maximum emission wavelength of the green emission spectrum can belong to a wavelength range of about 500 nm or more and less than 590 nm, and within that range, can belong to a wavelength range of about 510 nm to 580 nm, about 515 nm to 570 nm, 520 nm to 560 nm, 525 nm to 555 nm, 530 nm to 550 nm, 535 nm to 545 nm, or a combination thereof.
[0211] For example, the light-emitting layer 183 or the light-emitting material contained therein may include a phosphorescent material, a fluorescent material, or a combination thereof. For example, the light-emitting material may include an organic light-emitting material, and the organic light-emitting material may be a low molecular compound, a high molecular compound, or a combination thereof. The specific types of the phosphorescent material and the fluorescent material are not particularly limited and may be appropriately selected from known materials. For example, the light-emitting material may include an inorganic light-emitting material, and the inorganic light-emitting material may be an inorganic semiconductor, a quantum dot, a perovskite, or a combination thereof. The inorganic semiconductor may include a metal nitride, a metal oxide, or a combination thereof. The metal nitride, the metal oxide, or a combination thereof may include a group III metal such as aluminum, gallium, indium, or thallium, a group IV metal such as silicon, germanium, or tin, or a combination thereof. When the light-emitting material includes an inorganic light-emitting material, the light-emitting element 180 may be a quantum dot light-emitting diode, a perovskite light-emitting diode, or a micro light-emitting diode (μLED). Materials that can be used as the inorganic light-emitting material are known.
[0212] In an embodiment, the light emitting device 180 may further include auxiliary layers 184 and 185. The auxiliary layers 184 and 185 may be located between the first electrode 181 and the light emitting layer 183 and between the second electrode 182 and the light emitting layer 183, respectively. The auxiliary layers 184 and 185 may be charge auxiliary layers for controlling charge injection and / or mobility. The auxiliary layers 184 and 185 may each be one layer or two or more layers, for example, a hole injection layer, a hole transport layer, an electron blocking layer, an electron injection layer, an electron transport layer, a hole blocking layer, or a combination thereof. At least one of the auxiliary layers 184 and 185 may be omitted. Materials for each auxiliary layer may be appropriately selected from materials known for organic electroluminescent devices, etc.
[0213] Each sub-pixel PX 1 , P.X. 2 , P.X. 3 The light emitting elements 180 arranged in each sub-pixel PX may be the same or different. 1 , P.X. 2 , P.X. 3 The light emitting elements 180 arranged in the sub-pixels PX can emit light having the same or different emission spectra. 1 , P.X. 2 , P.X. 3 Each of the light-emitting elements 180 arranged in each of the sub-pixels PX may emit light in the blue emission spectrum, the green emission spectrum, or a combination thereof. 1 , P.X. 2 , P.X. 3 The light emitting elements 180 arranged in the pixel array 140 may be separated by pixel defining films (not shown).
[0214] Referring to FIG. 5c, the light emitting device 180 is a light emitting device having a tandem structure and includes a first electrode 181 and a second electrode 182 facing each other; a first light emitting layer 183a and a second light emitting layer 183b located between the first electrode 181 and the second electrode 182; a charge generation layer 186 located between the first light emitting layer 183a and the second light emitting layer 183b; and, optionally, auxiliary layers 184 and 185 located between the first electrode 181 and the first light emitting layer 183a and between the second electrode 182 and the second light emitting layer 183b.
[0215] The first electrode 181, the second electrode 182, and the auxiliary layers 184, 185 are as described above. The first light emitting layer 183a and the second light emitting layer 183b may emit light having the same or different emission spectrum. In one embodiment, the first light emitting layer 183a or the second light emitting layer 183b may emit light having a blue emission spectrum or a green emission spectrum. The charge generation layer 186 may inject charges into the first light emitting layer 183a and / or the second light emitting layer 183b and adjust the charge balance between the first light emitting layer 183a and the second light emitting layer 183b. The charge generation layer 186 may include, for example, an n-type layer and a p-type layer, and may include, for example, an electron transport material and / or a hole transport material containing an n-type dopant and / or a p-type dopant. The charge generation layer 186 may be one layer or two or more layers.
[0216] Referring to FIG. 5d, a light-emitting element (e.g., having a tandem structure) may include a first electrode 181 and a second electrode 182 facing each other; a first light-emitting layer 183a, a second light-emitting layer 183b and a third light-emitting layer 183c located between the first electrode 181 and the second electrode 182; a first charge generation layer 186a located between the first light-emitting layer 183a and the second light-emitting layer 183b; a second charge generation layer 186b located between the second light-emitting layer 183b and the third light-emitting layer 183c; and auxiliary layers 184, 185 optionally located between the first electrode 181 and the first light-emitting layer 183a and between the second electrode 182 and the third light-emitting layer 183c. The first electrode 181, the second electrode 182 and the auxiliary layers 184, 185 are as described above.
[0217] The first light emitting layer 183a, the second light emitting layer 183b, and the third light emitting layer 183c may emit light of the same or different emission spectrum. The first light emitting layer 183a, the second light emitting layer 183b, and the third light emitting layer 183c may emit blue light. In one embodiment, the first light emitting layer 183a and the third light emitting layer 183c may emit light of a blue emission spectrum, and the second light emitting layer 183b may emit light of a green emission spectrum. In another embodiment, the first light emitting layer 183a and the third light emitting layer 183c may emit light of a green emission spectrum, and the second light emitting layer 183b may emit light of a blue emission spectrum.
[0218] The first charge generation layer 186a can inject charges into the first light-emitting layer 183a and / or the second light-emitting layer 183b, and can adjust the charge balance between the first light-emitting layer 183a and the second light-emitting layer 183b. The second charge generation layer 186a can inject charges into the second light-emitting layer 183b and / or the third light-emitting layer 183c, and can adjust the charge balance between the second light-emitting layer 183b and the third light-emitting layer 183c. Each of the first and second charge generation layers 186a, 186b can be one layer or two or more layers.
[0219] Referring to FIG. 5 e , a light emitting device 180 includes a first electrode 181 , a second electrode 182 and a light emitting layer 183 including a plurality of nanostructures 187 . Either the first electrode 181 or the second electrode 182 may be an anode, and the other may be a cathode. The first electrode 181 and the second electrode 182 may be patterned electrodes according to the arrangement direction of a plurality of nanostructures 187, and may include, but are not limited to, conductive oxides such as indium tin oxide (ITO), indium zinc oxide (IZO), zinc oxide (ZnO), tin oxide (SnO), aluminum tin oxide (AlTO), and fluorine-doped tin oxide (FTO); silver (Ag), copper (Cu), aluminum (Al), gold (Au), titanium (Ti), chromium (Cr), nickel (Ni), alloys thereof, nitrides thereof (e.g., TiN); or combinations thereof.
[0220] The light-emitting layer 183 may include a plurality of nanostructures 187, and each subpixel PX 1 , P.X. 2 , P.X. 3 may include a plurality of nanostructures 187. The plurality of nanostructures 187 may be arranged in one direction, but is not limited thereto. The nanostructures 187 are compound semiconductors that emit light of a predetermined wavelength when a current is applied, and may be linear nanostructures such as nanorods or nanoneedles. The diameter or major axis of the nanostructures 187 may be, for example, several to several hundred nanometers, and the aspect ratio of the nanostructures 187 may be in the range of more than about 1, about 1.5 or more, about 2.0 or more, about 3.0 or more, about 4.0 or more, about 4.5 or more, about 5.0 or more, more than about 1 to 20, about 1.5 to 20, about 2.0 to 20, about 3.0 to 20, about 4.0 to 20, about 4.5 to 20, or about 5.0 to 20, or a combination thereof.
[0221] Each nanostructure 187 may include a p-type region 187p, an n-type region 187n, and a multiple quantum well region 187i, and may emit light in the multiple quantum well region 187i. The nanostructures 187 may include, for example, gallium nitride (GaN), indium gallium nitride (InGaN), aluminum gallium nitride (AlGaN), or a combination thereof, and may have, for example, a core-shell structure.
[0222] The nanostructures 187 may emit light having the same or different emission spectrums. In one embodiment, the first nanostructure 187a may emit light having a blue emission spectrum, for example, light having a maximum emission wavelength in a wavelength range of about 400 nm to less than 500 nm, about 410 nm to 490 nm, or about 420 nm to 480 nm.
[0223] FIG. 6 is a schematic cross-sectional view of a device (or display panel) according to an embodiment. Referring to FIG. 6, a light source (or light-emitting panel) may include an organic light-emitting diode that emits blue light (and optionally green light). The organic light-emitting diode may include two or more pixel electrodes formed on a substrate, a pixel defining film formed between adjacent pixel electrodes, an organic light-emitting layer formed on each pixel electrode, and a common electrode layer formed on the organic light-emitting layer. A thin film transistor and a substrate are disposed below the organic light-emitting diode. Pixel regions of the OLED are disposed corresponding to first, second, and third regions, which will be described later. Although the color conversion panel and the light-emitting panel are shown in a separated form in FIG. 6, the color conversion panel may be stacked directly above the light-emitting panel.
[0224] A laminate structure including a pattern of nanoparticle composites (e.g., a first region including red quantum dots and a second region including green quantum dots) and a substrate is disposed on the light source. Blue light emitted from the light source is incident on the first region and the second region to emit red and green light, respectively. The blue light emitted from the light source can pass through the third region. An element (a first optical filter or an excitation light blocking layer) that selectively blocks excitation light is disposed between the nanoparticle composite layer (R, G) and the substrate. If the excitation light includes blue light and green light, a green light blocking filter can be added to the third region. The first optical filter or excitation light blocking layer will be described in more detail below.
[0225] Such devices can be fabricated by combining the color conversion panel described above with a separately fabricated LED or OLED (e.g., emitting blue light and optionally green light), or alternatively, the devices can be fabricated by directly forming a pattern of nanoparticle composites on the LED or OLED.
[0226] In one embodiment of the color conversion panel or display device, the substrate may be a substrate including an insulating material. The substrate may be made of glass; polyesters such as polyethylene terephthalate (PET) and polyethylene naphthalate (PEN), various polymers such as polycarbonate and polyacrylate; polysiloxane (e.g., PDMS); Al 2 O 3 , ZnO, or other inorganic materials; or combinations thereof, but are not limited thereto. The thickness of the substrate can be appropriately selected in consideration of the substrate material, etc., and is not particularly limited. The substrate may be flexible. The substrate is configured to have a transmittance of 50% or more, 60% or more, 70% or more, 80% or more, or 90% or more for light emitted from the quantum dots.
[0227] A wiring layer including thin film transistors is formed on the substrate. The wiring layer may further include gate lines, storage voltage lines, gate insulating films, data lines, source electrodes, drain electrodes, semiconductors, protective films, etc. The detailed structure of the wiring layer may vary depending on the embodiment. The gate lines and storage voltage lines are electrically isolated from each other, and the data lines cross the gate lines and storage voltage lines insulated from each other. The gate electrodes, source electrodes, and drain electrodes respectively constitute a control terminal, an input terminal, and an output terminal of the thin film transistors. The drain electrodes are electrically connected to pixel electrodes described below.
[0228] The pixel electrode can function as an electrode (e.g., an anode) of the display device. The pixel electrode can be formed of a transparent conductive material such as indium tin oxide (ITO) or indium zinc oxide (IZO). The pixel electrode can also be formed of a light-shielding material such as gold (Au), platinum (Pt), nickel (Ni), tungsten (W), chromium (Cr), molybdenum (Mo), iron (Fe), cobalt (Co), copper (Cu), palladium (Pd), titanium (Ti), etc. The pixel electrode can have a two-layer structure in which the above-mentioned transparent conductive material and the above-mentioned light-shielding material are sequentially stacked.
[0229] A pixel defining layer (PDL) may be formed between two adjacent pixel electrodes, overlapping the ends of the pixel electrodes to divide the pixel electrodes into pixel units. The pixel defining layer is an insulating layer, and can electrically isolate the two or more pixel electrodes.
[0230] The pixel definition layer may cover only a portion of an upper surface of the pixel electrode, and the remaining portion of the pixel electrode not covered by the pixel definition layer may form an opening. An organic light emitting layer, which will be described later, may be formed on the area defined as the opening.
[0231] The organic light emitting layer is defined as each pixel region by the pixel electrode and the pixel defining layer. That is, a region in which one organic light emitting unit layer is formed and in contact with one pixel electrode separated by the pixel defining layer can be defined as one pixel region. In the display device according to the embodiment, the organic light emitting layer can be defined as a first pixel region, a second pixel region, and a third pixel region, and each pixel region is spaced apart by a predetermined distance by the pixel defining layer.
[0232] The organic light emitting layer may emit a third light in the visible light region or in the UV region. The first to third pixel regions of the organic light emitting layer may all emit the third light. In one embodiment, the third light may include light having a high energy in the visible light region, for example, blue light (and optionally green light). When all the pixel regions of the organic light emitting layer are designed to emit the same light, the pixel regions of the organic light emitting layer may be formed of the same or similar material or may exhibit the same or similar physical properties. Therefore, the difficulty of the process of forming the organic light emitting layer can be significantly reduced, and such a display device can be easily applied to a process of enlarging the size / area of the display device. However, the organic light emitting layer according to an embodiment is not necessarily limited thereto, and the organic light emitting layer may be configured to emit two or more different lights.
[0233] The organic light emitting layer includes an organic light emitting unit layer for each pixel region, and each organic light emitting unit layer may further include auxiliary layers (eg, a hole injection layer, a hole transport layer, an electron transport layer, etc.) in addition to the light emitting layer.
[0234] The common electrode can function as a cathode of the display device. The common electrode can be formed of a transparent conductive material such as indium tin oxide (ITO) or indium zinc oxide (IZO). The common electrode can be integrally formed on the organic light emitting layer.
[0235] A planarization or passivation layer (not shown) may be formed on the common electrode. The planarization layer may include an insulating material (e.g., transparent) to ensure electrical insulation from the common electrode.
[0236] In one embodiment, the display device further includes a lower substrate, a polarizer disposed under the lower substrate, and a liquid crystal layer interposed between the laminated structure and the lower substrate, the laminated structure being disposed such that the light emitting layer faces the liquid crystal layer. The display device may further include a polarizer between the liquid crystal layer and the light emitting layer. The light source may further include an LED and, optionally, a light guide plate.
[0237] A display device (e.g., a liquid crystal display device) according to a non-limiting embodiment will be described with reference to the drawings. Fig. 7 is a schematic cross-sectional view of a liquid crystal display device according to a non-limiting embodiment. Referring to Fig. 7, the display device according to the embodiment includes a liquid crystal panel 200, a polarizer 300 disposed below the liquid crystal panel 200, and a backlight unit (BLU) disposed below the polarizer 300.
[0238] The liquid crystal panel 200 includes a lower substrate 210, a laminated structure, and a liquid crystal layer 220 interposed between the laminated structure and the lower substrate 210. The laminated structure includes a transparent substrate 240 and a self-emitting layer 230 including a pattern of a quantum dot polymer composite. The lower substrate 210, also called an array substrate, may be a transparent insulating material substrate. The substrate has been described above. A wiring board 211 is provided on the upper surface of the lower substrate 210. The wiring board 211 may include, but is not limited to, a plurality of gate lines (not shown) and data lines (not shown) defining pixel regions, thin film transistors provided adjacent to intersections of the gate lines and the data lines, and pixel electrodes for each pixel region. The specific contents of such a wiring board are known and are not particularly limited.
[0239] A liquid crystal layer 220 is provided on the wiring board 211. The liquid crystal layer 220 may include alignment films 221 above and below the layer for initial alignment of the liquid crystal material contained therein. Specific details regarding the liquid crystal material and the alignment film (e.g., liquid crystal material, alignment film material, method of forming the liquid crystal layer, thickness of the liquid crystal layer, etc.) are known and are not particularly limited.
[0240] A lower polarizing plate 300 is provided under the lower substrate. The material and structure of the polarizing plate 300 are known and are not particularly limited. A backlight unit (e.g., emitting blue light) is provided under the polarizing plate 300. An upper optical element or polarizing plate 300 may be provided between the liquid crystal layer 220 and the transparent substrate 240, but is not limited thereto. For example, the upper polarizing plate is disposed between the liquid crystal layer 220 and the light emitting layer 230. The polarizing plate may be any polarizer that can be used in a liquid crystal display device. The polarizing plate may be, but is not limited to, TAC (triacetyl cellulose) having a thin thickness of 200 um or less. In another embodiment, the upper optical element may be a refractive index adjustment coating without a polarization function.
[0241] The backlight unit includes a light source 110. The light source can emit blue or white light. The light source can include, but is not limited to, a blue LED, a white LED, a white OLED, or a combination thereof.
[0242] The backlight unit may further include a light guide plate 120. In one embodiment, the backlight unit may be an edge type. For example, the backlight unit may include a reflector (not shown), a light guide plate (not shown) provided on the reflector to provide a surface light source to the liquid crystal panel 200, and / or one or more optical sheets (not shown) located on the light guide plate, such as a diffusion plate, a prism sheet, etc., but is not limited thereto. The backlight unit may not include a light guide plate. In one embodiment, the backlight unit may be a direct lighting type. For example, the backlight unit may include a reflector (not shown), a number of fluorescent lamps arranged at regular intervals on the reflector, or a driving board for LEDs on which a number of light emitting diodes are arranged, and a diffusion plate and one or more optional optical sheets thereon. Details of such a backlight unit (for example, details of each component such as light emitting diodes, fluorescent lamps, light guide plate, various optical sheets, and reflector) are known and are not particularly limited.
[0243] A black matrix 241 is provided on the bottom surface of the transparent substrate 240, the black matrix 241 including an opening and shielding gate lines, data lines, thin film transistors, etc. of a wiring board provided on the lower substrate. For example, the black matrix 241 may have a lattice shape. A self-emitting layer 230 having a nanoparticle-polymer composite pattern including a first region R emitting a first light (e.g., red light), a second region G emitting a second light (e.g., green light), and a third region B emitting / transmitting, for example, blue light is provided in the opening of the black matrix 241. If desired, the self-emitting layer may further include one or more fourth regions. The fourth region may include quantum dots emitting light of a color (e.g., cyan, magenta, and yellow) different from the light emitted from the first to third regions.
[0244] The patterned sections of the light emitting layer 230 may be repeated corresponding to pixel regions formed on the lower substrate. A transparent common electrode 231 may be provided on the self-emissive color filter layer. The third region B that transmits / emits blue light may be a transparent color filter that does not change the emission spectrum of the light source. In this case, the blue light emitted from the backlight unit may be incident in a polarized state through the polarizer and the liquid crystal layer and emitted as is. If necessary, the third region may include quantum dots that emit blue light.
[0245] As described above, if desired, the display device or light emitting element of an embodiment may further include an excitation light blocking layer or a first optical filter layer (hereinafter, referred to as a first optical filter layer). The first optical filter layer is disposed between the bottom surface of the first region R and the second region G and a substrate (e.g., the upper substrate 240) or on the upper surface of the substrate. The first optical filter layer is a sheet having an opening in a portion corresponding to a pixel region (third region) that displays blue, and may be formed in a portion corresponding to the first and second regions. That is, the first optical filter layer may be integrally formed in a remaining portion except for a portion overlapping with the third region as shown in Figs. 2a, 2b, and 3, but is not limited thereto. Two or more first optical filter layers may be disposed separately in the first and second regions and optionally in a portion overlapping with the third region. If the light source includes a green light emitting element, a green light blocking layer is disposed on the third region.
[0246] The first optical filter layer can, for example, block light in a certain wavelength range within the visible light range and transmit light in the remaining wavelength range, for example, block blue light (or green light) and transmit light other than blue light (or green light). The first optical filter layer can, for example, transmit green light, red light and / or yellow light, which is a mixture of these colors. The first optical filter layer can transmit blue light and block green light, and is disposed on the blue light emitting pixels. The first optical filter layer can substantially block the excitation light and transmit light in a desired wavelength range, and the transmittance of the first optical filter layer for light in the desired wavelength range can be about 70% or more, 80% or more, 90% or more, or even 100%.
[0247] A first optical filter layer that selectively transmits red light may be disposed in a position overlapping the red light emitting section, and a first optical filter layer that selectively transmits green light may be disposed in a position overlapping the green light emitting section. The first optical filter layer can include at least one of a first region that blocks (e.g., absorbs) blue and red light and selectively transmits light in a predetermined range (e.g., about 500 nm or more, about 510 nm or more, or about 515 nm or more and about 550 nm or less, about 545 nm or less, about 540 nm or less, about 535 nm or less, about 530 nm or less, about 525 nm or less, or about 520 nm or less), and a second region that blocks (e.g., absorbs) blue and green light and selectively transmits light in a predetermined range (e.g., about 600 nm or more, about 610 nm or more, or about 615 nm or more and about 650 nm or less, about 645 nm or less, about 640 nm or less, about 635 nm or less, about 630 nm or less, about 625 nm or less, or about 620 nm or less). If the light source emits a mixture of blue and green light, the first optical filter may further include a third region that selectively transmits blue light and blocks green light.
[0248] The first region is disposed at a position overlapping the green light-emitting section, the second region is disposed at a position overlapping the red light-emitting section, and the third region is disposed at a position overlapping the blue light-emitting section. The first region, the second region, and optionally the third region may be optically isolated. Such a first optical filter layer can contribute to improving the color purity of the display device.
[0249] The display element may further include a second optical filter layer (e.g., a red / green light or yellow light recycling layer) disposed between the light emitting layer and the liquid crystal layer (e.g., between the light emitting layer and the upper polarizer) and transmitting at least a portion of the third light (excitation light) and reflecting at least a portion of the first light and / or the second light. The first light may be red light, the second light may be green light, and the third light may be blue light. The second optical filter layer may transmit only the third light (B) in a blue light wavelength region having a wavelength region of 500 nm or less, and may reflect light in a wavelength region exceeding 500 nm, i.e., green light (G), yellow light, red light (R), etc., without passing through the second optical filter layer 140. The reflected green light and red light pass through the first and second regions and are emitted to the outside of the display device 10.
[0250] The second optical filter layer or the first optical filter layer may be formed of a unitary layer having a relatively flat surface. The first optical filter layer may include a polymer thin film containing a dye and / or pigment that absorbs light of a wavelength to be blocked. The second optical filter layer and the first optical filter layer may include a single layer having a low refractive index, for example, a transparent thin film having a refractive index of 1.4 or less, 1.3 or less, or 1.2 or less. The second optical filter layer or the first optical filter layer having a low refractive index may be, for example, a porous silicon oxide, a porous organic material, a porous organic / inorganic composite, or a combination thereof.
[0251] The first optical filter layer or the second optical filter layer may include a plurality of layers having different refractive indices. Two layers having different refractive indices may be formed by alternately stacking them. For example, a material having a high refractive index and a material having a low refractive index may be alternately stacked to form the first / second optical filter layer.
[0252] Specific examples are presented below. However, the examples described below are merely for the purpose of specifically illustrating and explaining the invention, and should not be construed as limiting the scope of the invention.
[0253] [Example] Analysis method [1] Photoluminescence analysis Photoluminescence (PL) spectra of the prepared nanoparticles and the complexes containing the same were obtained using a Hitachi F-7000 spectrophotometer at an excitation wavelength of 450 nm. [2] Optical property analysis of the composite (QY) The amount of incident light having a wavelength of 450 nm (B) was measured using an integrating hemisphere of an absolute quantum efficiency measurement device (QE-2100, Otsuka). Next, the QD-polymer composite was placed in the integrating hemisphere, and the amount of incident light was irradiated to measure the amount of the first light emitted from the composite (A) and the amount of incident light that passed through the composite (B'). From the measured values, the incident light absorptance, external quantum efficiency, and internal quantum efficiency were calculated according to the following formulas. Incident light absorption rate (%) = [(B-B') / B] x 100 External quantum efficiency (EQE,%) = [A / B] x 100 Internal quantum efficiency (IQE,%) = [A / (B-B')] x 100
[0254] [3] Retention rate analysis The semiconductor nanoparticle-polymer composite obtained by polymerization was heat-treated at 180° C. for 30 minutes, and the retention rate was measured by the following formula. Retention rate (%)=[EQE2 / EQE1]×100 In the above formula, EQE1 is the external quantum efficiency of the semiconductor nanoparticle-polymer composite before heat treatment after polymerization, and EQE2 is the external quantum efficiency of the semiconductor nanoparticle-polymer composite after heat treatment. [4]XPS analysis XPS analysis was performed using an XPS equipment (Quantera II) (manufactured by ULCAC-PHI) system.
[0255] Reference Example 1: A 0.06M silver precursor-containing solution (hereinafter referred to as silver precursor) was prepared by dissolving silver acetate in oleylamine. A 1M sulfur precursor-containing solution (hereinafter referred to as sulfur precursor) was prepared by dispersing sulfur in oleylamine. A 0.2M indium precursor-containing solution (hereinafter referred to as indium precursor) was prepared by dissolving indium chloride in ethanol. Gallium acetylacetonate, octadecene (ODE), and dodecanethiol were placed in a 100 mL reaction flask and heated at 120° C. under vacuum for 10 minutes. The flask was cooled to room temperature, and the gas in the flask was replaced with nitrogen. The silver precursor, sulfur precursor, and indium precursor were then placed in the flask, and the flask temperature was raised to the reaction temperature (210° C.) and reacted within 60 minutes. The flask temperature was lowered to 180° C., trioctylphosphine (TOP) was added, and the mixture was cooled to room temperature. Hexane and ethanol were added to the resulting mixture to promote precipitation. The resulting first semiconductor nanocrystals were collected by centrifugation and redispersed in toluene. The molar ratio of indium precursor, gallium precursor, and sulfur precursor used was 1:2.3:4.8.
[0256] Gallium chloride was dissolved in toluene to prepare a 4.5 M gallium precursor-containing solution (hereinafter, gallium precursor). Dimethylthiourea (DMTU), oleylamine, and dodecanethiol were placed in a flask and vacuum-treated at 120°C for 10 minutes. 2 The inside of the reaction flask was replaced with hexane, and the flask was heated to 240°C (first temperature), after which the first semiconductor nanocrystal (emission wavelength 524 nm, half width 44 nm) prepared above, as well as the gallium precursor and silver precursor, were added. The reactor was then heated to 320°C (second temperature) and reacted for about 10 minutes (first hour). The temperature of the reaction solution was raised to 180°C, trioctylphosphine was added, and the solution was cooled to room temperature. Hexane and ethanol were added to precipitate the nanoparticles, and the resulting semiconductor particles were collected by centrifugation and redispersed in toluene. The molar ratio of gallium, silver and sulfur precursors used is 1:0.5:1.
[0257] Example 1: Preparation of Ligand-Exchanged Semiconductor Nanoparticles and Ink Compositions / Complexes [1] Ligand exchange reaction A toluene dispersion of the semiconductor nanoparticles obtained in Reference Example 1 was prepared. 2-(4-fluorophenyl)acetic acid) having the following chemical formula (CAS no: 405-50-5, purchased from Sigma-Aldrich) was dissolved in toluene to prepare a first ligand compound solution: [ka] A zinc chloride solution (solvent: acetone) was prepared. The first ligand compound solution and zinc chloride solution were mixed with the toluene dispersion of the semiconductor nanoparticles, and the mixture was stirred at room temperature for 3 hours to carry out a ligand exchange reaction. Next, hexane was added to the reaction solution to induce particle precipitation, and the ligand-exchanged semiconductor nanoparticles were recovered by centrifugation and dried. The content of the first organic ligand compound relative to 1 mole of the quantum dots was 2000 moles. The content of zinc chloride was 5 mole % relative to the organic ligand content. After the ligand exchange, the QY (absolute quantum efficiency, solution) of the semiconductor nanoparticles was measured, and the results are summarized in Table 1.
[0258] [2] Preparation of ink composition and formation of composite An ink composition was prepared by adding the ligand-exchanged semiconductor nanoparticles obtained in [1], titanium oxide fine particles, and an initiator to hexanediol diacrylate (monomer, Cas No. 13048-33-4, purchased from Sigma-Aldrich). The quantum dot content, titanium oxide fine particles, and initiator content in the composition are 20 wt%, 5 wt%, and 1 wt%, respectively, based on the total weight of the composition, with the remainder being monomer. The prepared composition was deposited on a substrate, exposed (exposure amount 4 Joule, wavelength 395 nm) and photopolymerized to obtain a film with a thickness of 7 um. The produced film was post baked at 180° C. for 30 minutes, and the emission wavelength, half width, external quantum efficiency, internal quantum efficiency, and retention rate were measured. The results are summarized in Tables 1 and 3.
[0259] [3] XPS analysis was performed on the produced film to measure the fluorine content relative to indium, fluorine content relative to silver, and fluorine content relative to sulfur, respectively, and the results are summarized in Table 2 and Figure 8. The binding energy of the fluorine peak is 687.1 eV.
[0260] Example 2: [1] Ligand-exchanged semiconductor nanoparticles were obtained in the same manner as in Example 1, except that the content of the first organic ligand was 4,000 moles per mole of semiconductor nanoparticles. After the ligand exchange, the QY (absolute quantum efficiency, solution) of the semiconductor nanoparticles was measured, and the results are summarized in Table 1. [2] Except for using the ligand-exchanged nanoparticles prepared above, a composite film was obtained in the same manner as in Example 1. The prepared film was post baked at 180°C for 30 minutes, and the half-width, emission wavelength, external quantum efficiency, internal quantum efficiency, and retention rate were measured, and the results are summarized in Tables 1 and 3. [3] XPS analysis was performed on the produced film to measure the fluorine content relative to indium, fluorine content relative to silver, and fluorine content relative to sulfur, respectively, and the results are summarized in Table 2 and Figure 8. The binding energy of the fluorine peak is 686.94 eV.
[0261] Example 3: [1] Ligand-exchanged semiconductor nanoparticles were obtained in the same manner as in Example 1, except that the content of the first organic ligand was 6,000 moles per mole of semiconductor nanoparticles. After the ligand exchange, the QY (absolute quantum efficiency, solution) of the semiconductor nanoparticles was measured, and the results are summarized in Table 1. [2] Except for using the ligand-exchanged nanoparticles prepared above, a composite film was obtained in the same manner as in Example 1. The prepared film was post baked at 180°C for 30 minutes, and the emission wavelength, half-width, external quantum efficiency, internal quantum efficiency, and retention rate were measured, and the results are summarized in Tables 1 and 3. [3] XPS analysis was performed on the produced film to measure the fluorine content relative to indium, fluorine content relative to silver, and fluorine content relative to sulfur, respectively, and the results are summarized in Table 2 and Figure 8. The binding energy of the fluorine peak is 686.6 eV.
[0262] Comparative Example 1 An ink composition was prepared using semiconductor nanoparticles that were not ligand-exchanged, and it was confirmed that the semiconductor particles did not significantly aggregate within the composition to form a coating liquid capable of forming a complex.
[0263] Comparative Example 2 [1] Ligand-exchanged nanoparticles were prepared in the same manner as in Example 1, except that a compound represented by the following formula was used in an amount of 4,000 moles per mole of semiconductor nanoparticles instead of the first organic compound: [ka] n1=7 After the ligand exchange, the QY (absolute quantum efficiency, solution) of the semiconductor nanoparticles was measured, and the results are summarized in Table 1. [2] Except for using the ligand-exchanged nanoparticles prepared above, a composite film was obtained in the same manner as in Example 1. The prepared film was post baked at 180°C for 30 minutes, and the emission wavelength, half-width, external quantum efficiency, internal quantum efficiency, and retention rate were measured, and the results are summarized in Tables 1 and 3. [3] XPS analysis was performed on the produced film to measure the fluorine content relative to indium, fluorine content relative to silver, and fluorine content relative to sulfur, respectively, and the results are summarized in Table 2 and Figure 8.
[0264] Comparative Example 3 [1] Ligand-exchanged nanoparticles were prepared in the same manner as in Example 1, except that a compound represented by the following formula was used in an amount of 4,000 moles per mole of semiconductor nanoparticles instead of the first organic compound: [ka] After the ligand exchange, the QY (absolute quantum efficiency, solution) of the semiconductor nanoparticles was measured, and the results are summarized in Table 1. [2] Except for using the ligand-exchanged nanoparticles prepared above, a composite film was obtained in the same manner as in Example 1. The prepared film was post baked at 180°C for 30 minutes, and the emission wavelength, half-width, external quantum efficiency, internal quantum efficiency, and retention rate were measured, and the results are summarized in Tables 1 and 3. [3] XPS analysis was performed on the produced film to measure the fluorine content relative to indium, fluorine content relative to silver, and fluorine content relative to sulfur, respectively, and the results are summarized in Table 2 and Figure 8.
[0265] Comparative Example 4 [1] Ligand-exchanged nanoparticles were prepared in the same manner as in Example 1, except that a compound represented by the following formula was used in an amount of 4,000 moles per mole of semiconductor nanoparticles instead of the first organic compound: [ka] After the ligand exchange, the QY (absolute quantum efficiency, solution) of the semiconductor nanoparticles was measured, and the results are summarized in Table 1. [2] Except for using the ligand-exchanged nanoparticles prepared above, a composite film was obtained in the same manner as in Example 1. The prepared film was post baked at 180°C for 30 minutes, and the emission wavelength, half-width, external quantum efficiency, internal quantum efficiency, and retention rate were measured, and the results are summarized in Tables 1 and 3. [3] XPS analysis was performed on the produced film to measure the fluorine content relative to indium, fluorine content relative to silver, and fluorine content relative to sulfur, respectively, and the results are summarized in Table 2 and Figure 8.
[0266] [Table 1]
[0267] From the results in Table 1, it can be seen that the ligand-exchanged quantum dots of the examples can exhibit significantly higher quantum yields than the comparative examples, while the ligand-exchanged quantum dots of the comparative examples suffer from a significant decrease in quantum dot efficiency due to ligand exchange.
[0268] [Table 2]
[0269] [Table 3]
[0270] From the results in Table 3, it was confirmed that the semiconductor nanoparticle-polymer composite of the Examples not only exhibited significantly improved luminescence properties compared to the Comparative Examples, but also showed virtually no decrease in luminance efficiency due to heat treatment, and may even have an increased luminance efficiency. It was confirmed that the semiconductor nanoparticle-polymer composite of the Comparative Examples showed a significant decrease in luminance efficiency due to heat treatment.
[0271] Although the embodiments have been described in detail above, the scope of the invention is not limited thereto, and various modifications and improvements made by those skilled in the art using the basic concepts defined in the claims also fall within the scope of the invention.
Claims
1. 1. An ink composition comprising: The ink composition includes semiconductor nanoparticles, a first organic ligand, and a polymerizable monomer, the semiconductor nanoparticles include a Group 11-13-16 compound including silver, indium, gallium, and sulfur, the first organic ligand includes an aromatic group and fluorine, and the content of the semiconductor nanoparticles in the ink composition is 1 wt % or more and 70 wt % or less based on the total weight of the ink composition.
2. The ink composition of claim 1 , wherein the first organic ligand further comprises a functional group configured to bind to a surface of the semiconductor nanoparticle.
3. 2. The ink composition of claim 1, wherein the semiconductor nanoparticles have a charge balance value, calculated by the following formula: charge balance value={[Ag]+3x([In]+[Ga])+2x[Zn]} / (2x[S]) where [Ag], [In], [Ga], [Zn] and [S] are the molar contents of silver, indium, gallium and sulfur, respectively, in the nanoparticles.
4. The semiconductor nanoparticles, the molar ratio of gallium to indium (Ga / In) is greater than or equal to 2.5 and less than or equal to 10; a molar ratio of sulfur to indium of 3 or more and 25 or less; or 2. The ink composition of claim 1, wherein the molar ratio of gallium to sulfur is greater than or equal to 0.1 and less than or equal to 1.
5. The ink composition of claim 1 , wherein the semiconducting nanoparticles further comprise zinc.
6. The semiconductor nanoparticles, The molar ratio of zinc to indium (the molar ratio of zinc to the total of zinc, silver, indium, and gallium) is 0.1 or more and 20 or less; the molar ratio of zinc to sulfur is greater than or equal to 0.01 and less than or equal to 0.9; or 6. The ink composition of claim 5, wherein the relative molar ratio of zinc is greater than or equal to 0.25 and less than or equal to 0.
9.
7. The ink composition according to claim 1 , wherein the content of the semiconductor nanoparticles in the ink composition is 14% or more and 65% or less.
8. 2. The ink composition of claim 1, wherein the first organic ligand comprises a compound represented by Chemical Formula 1: [Chemical formula 1] A-L-Ar In the above formula, A is a functional group configured to interact with the surface of the semiconductor nanoparticle; L includes a single bond, a substituted or unsubstituted aliphatic hydrocarbon group having 1 to 40 carbon atoms, a substituted or unsubstituted aromatic hydrocarbon group having 6 to 40 carbon atoms, a substituted or unsubstituted alicyclic hydrocarbon group having 3 to 40 carbon atoms, -CO-, -O-, -COO-, -S-, -SO-, -NHCO-, -NH-, or a combination thereof; Ar is a fluorine-containing aromatic group having 6 to 40 carbon atoms.
9. The ink composition of claim 8 , wherein the functional groups include carboxy groups, carboxylate groups, or a combination thereof.
10. 2. The ink composition of claim 1, wherein the first organic ligand comprises fluorobenzoic acid, a fluorophenyl carboxylic acid compound, a fluoroalkyl group-substituted phenyl carboxylic acid compound, a fluoroalkenyl group-substituted phenyl carboxylic acid compound, a fluoroalkynyl group-substituted phenyl carboxylic acid compound, a mercaptofluorobenzene, a fluorophenyl thiol compound, a fluoroalkyl group-substituted phenyl thiol compound, a fluoroalkenyl group-substituted phenyl thiol compound, a fluoroalkynyl group-substituted phenyl thiol compound, or a combination thereof.
11. The ink composition of claim 1 , wherein the first organic ligand has a molecular weight of 50 g / mol or more and 300 g / mol or less.
12. 2. The ink composition according to claim 1, wherein the semiconductor nanoparticles have an absolute quantum yield of 85% or more and 99% or less, and a half-value width of 10 nm to 40 nm.
13. the ink composition provides, by polymerization, a semiconductor nanoparticle-polymer composite comprising a matrix containing a polymerization product of the monomer and semiconductor nanoparticles disposed or dispersed within the matrix; the semiconductor nanoparticle-polymer composite further comprises the first organic ligand; 2. The ink composition according to claim 1, wherein when the semiconductor nanoparticle-polymer composite is heat-treated at 180° C. for 30 minutes, the retention rate calculated by the following formula is 95% or more: Retention rate (%) = [EQE2 / EQE1] x 100 In the above formula, EQE1 is the external quantum efficiency of the semiconductor nanoparticle-polymer composite before heat treatment after polymerization, and EQE2 is the external quantum efficiency of the semiconductor nanoparticle-polymer composite after heat treatment.
14. 1. A semiconductor nanoparticle-polymer composite comprising: the semiconductor nanoparticle-polymer composite comprises a matrix, semiconductor nanoparticles dispersed within the matrix, and fluorine; The semiconductor nanoparticles include a Group 11-13-16 compound including silver, indium, gallium, and sulfur; The semiconductor nanoparticle-polymer composite, wherein the molar ratio of fluorine to sulfur (F / S) is greater than 0 and less than or equal to 5.
15. 15. The semiconductor nanoparticle-polymer composite of claim 14, wherein the molar ratio of fluorine to indium (F / In) in said semiconductor nanoparticle-polymer composite is greater than 0 and less than or equal to 10.
16. 15. The semiconductor nanoparticle-polymer composite of claim 14, wherein the molar ratio of fluorine to silver (F / Ag) in said semiconductor nanoparticle-polymer composite is greater than 0 and less than or equal to 5.
17. The semiconductor nanoparticle-polymer composite according to claim 14, wherein the external quantum efficiency (EQE) of the semiconductor nanoparticle-polymer composite is 30% or more when the semiconductor nanoparticle-polymer composite is irradiated with incident light having a wavelength of 450 nm and the EQE is calculated by the following formula: External quantum efficiency (%) = [A / B] x 100 A: Amount of the first light emitted from the semiconductor nanoparticle-polymer composite B: The amount of incident light.
18. An electronic device comprising the semiconductor nanoparticle-polymer composite of claim 14.
19. A display device comprising the semiconductor nanoparticle-polymer composite according to claim 14.